Protective lamination

JP2026534492APending Publication Date: 2026-10-16W L GORE & ASSOC GMBH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026518993
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-27
Publication Date
2026-10-16

Smart Images

  • Figure 2026534492000001
    Figure 2026534492000001
  • Figure 2026534492000002
    Figure 2026534492000002
  • Figure 2026534492000003
    Figure 2026534492000003
Patent Text Reader

Abstract

This disclosure relates to flame-retardant laminates that can be used in the manufacture of flame-retardant textiles and flame-retardant clothing. The laminates described herein enable the manufacture of flame-retardant laminates using non-flame-retardant textiles. The use of these non-flame-retardant textiles makes it possible to provide laminates that are significantly lighter, softer to the touch, more breathable, more durable, allow for a wider range of color production, have better moisture management properties, superior mechanical strength, and are more environmentally friendly compared to flame-retardant laminates made using inherently flame-retardant textiles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a protective laminate comprising multiple textile layers. In particular, this protective laminate can provide protection from flash fires and arc discharges. [Background technology]

[0002] For professionals working in hazardous environments where there is a possibility of short-term exposure to flames or arc discharges, protective laminates and protective clothing are required to mitigate injuries. Protective equipment for workers exposed to these conditions should provide a degree of protection that allows the wearer to quickly and safely evacuate from the hazard, rather than repairing the hazard itself.

[0003] Traditionally, clothing designed to protect against short-duration flash fires or flash discharges has been relatively heavy and required multiple layers, each layer providing a further level of protection against the heat of exposure. Such clothing is made of multiple layers, including non-flammable, non-melting fabrics made from materials such as aramid, polybenzimidazole (PBI), poly-p-phenylene-2,6-benzobisoxazole (PBO), modacryl blends, polyamines, carbon, polyacrylonitrile (PAN), and blends and combinations thereof. While these fabrics are inherently flame-retardant and frequently used by firefighters, they have several limitations. Specifically, achieving the desired level of protection requires relatively heavy and bulky fabrics. Typically, these fabrics can have a base weight exceeding 400 grams / square meter. The fibers used to form these fabrics are very expensive, difficult to dye and print, and may lack sufficient abrasion resistance. Furthermore, these fibers have higher water absorption and inferior feel compared to nylon or polyester-based fabrics. In environments with potential arc flash exposure and / or flash fires, lightweight, breathable, water-resistant, and burn-resistant clothing is sometimes required to achieve optimal user performance. There remains a need for protective clothing that is waterproof, flame-retardant (FR), and arc-flash resistant, minimizing or eliminating the use of typical non-combustible, non-melting fabrics, such as those used in firefighting operations. [Overview of the Initiative]

[0004] In a first embodiment, the disclosure relates to a laminate comprising a) a first textile layer, b) a first heat-reactive material layer, c) a carrier layer containing porous polyethylene, d) a second heat-reactive material layer, and e) a second textile layer. In the embodiments described herein, the first heat-reactive material layer and the second heat-reactive material layer each independently comprise a polymer resin and an expandable graphite. In any of the embodiments described above, the expandable graphite expands by at least about 900 micrometers when heated to about 280°C, as measured by a TMA expansion test.

[0005] Furthermore, in any embodiment described herein, the first heat-reactive material layer is positioned between the first textile layer and the carrier layer, and the second heat-reactive material layer is positioned between the carrier layer and the second textile layer.

[0006] In the second embodiment, each thermally reactive material layer is applied continuously or discontinuously and independently.

[0007] In any of the embodiments described above, each heat-reactive material layer may have a pattern shape of discontinuous dots, lines, or grids.

[0008] In all of the embodiments described above, the expandable graphite expands by at least about 900 micrometers when heated to 280°C, as measured by a TMA expansion test.

[0009] In any of the embodiments described above, at least one of the first heat-reactive material layer and the second heat-reactive material layer contains a flame retardant additive.

[0010] In any of the above embodiments, the first textile layer contains or is essentially composed of meltable fibers. In any of the above embodiments, the first textile layer contains or is essentially composed of non-meltable fibers. In any of the above embodiments, the first textile layer contains or is essentially composed of a mixture of meltable and non-meltable fibers.

[0011] In any of the aforementioned embodiments, the first textile layer may comprise meltable fibers in a range of 0% to 100%, based on the total mass of the meltable fibers and non-meltable fibers in the first textile layer. In other embodiments, the first textile layer may comprise more than 0% to 100% of meltable fibers, or 0.5% to 100% of meltable fibers, or 1% to 100% of meltable fibers, or 1% to 99% of meltable fibers, or 3% to 100% of meltable fibers, or 5% to 100% of meltable fibers, or 10% to 100% of meltable fibers, or 20% to 100% of meltable fibers, or 25% to 100% of meltable fibers, or 30% to 100% of meltable fibers, or 35% to 100% of meltable fibers, or 40% to 100% of meltable fibers, or 50% to 100% of meltable fibers, or 60% to 100% of meltable fibers, or 70% to 100% of meltable fibers, or 80% to 100% of meltable fibers, or 90% to 100% of meltable fibers. In other embodiments, the first textile comprises a combination of 1% to 99% non-meltable fibers and 1% to 99% meltable fibers, where the mass percentages are based on the total mass of fibers in the first textile layer. Each percentage is based on the total mass of fibers in the first textile layer.

[0012] In some of the above embodiments, the first textile layer may comprise 100% nylon textile. In some of the above embodiments, the first textile layer may comprise 100% polyester textile. In other embodiments, the first textile layer may be a cotton textile comprising up to 100% cotton. In other embodiments, the first textile layer may be a wool textile comprising up to 100% wool.

[0013] In yet another embodiment, the first textile layer may comprise a mixture of nylon and cotton, for example, a mixture in the range of 30% to 70% nylon and 30% to 70% cotton, or a mixture in the range of 30% to 68% nylon and 30% to 68% cotton, and an antistatic agent of about 5 mass% or less based on the total mass of the textile.

[0014] In yet another embodiment, the first textile layer may include a mixture of polyester and cotton, for example, a mixture in the range of 30% to 70% polyester and 30% to 70% cotton, or a mixture in the range of 30% to 68% polyester and 30% to 68% cotton, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile.

[0015] In any of the embodiments described above, the second textile layer contains or is essentially composed of meltable fibers. In any of the embodiments described above, the second textile layer contains or is essentially composed of non-meltable fibers. In any of the embodiments described above, the second textile layer contains or is essentially composed of a mixture of meltable and non-meltable fibers.

[0016] In any of the embodiments described above, the second textile layer may contain fusible fibers in a range of 0% to 100%, based on the total mass of fusible and non-fusible fibers in the second textile layer. In other embodiments, the second textile layer may contain more than 0% to 100% meltable fibers, or 0.5% to 100% meltable fibers, or 1% to 100% meltable fibers, or 1% to 99% meltable fibers, or 3% to 100% meltable fibers, or 5% to 100% meltable fibers, or 10% to 100% meltable fibers, or 20% to 100% meltable fibers, or 25% to 100% meltable fibers, or 30% to 100% meltable fibers, or 35% to 100% meltable fibers, or 40% to 100% meltable fibers, or 50% to 100% meltable fibers, or 60% to 100% meltable fibers, or 70% to 100% meltable fibers, or 80% to 100% meltable fibers, or 90% to 100% meltable fibers. In other embodiments, the second textile layer includes a combination of fused and non-fused fibers, comprising 1% to 99% non-fused fibers and 1% to 99% fused fibers. Each percentage is based on the total mass of fibers in the second textile layer.

[0017] In some embodiments described above, the second textile layer may include a 100% nylon textile. In other embodiments, the second textile layer may be a 100% polyester textile. In other embodiments, the second textile layer may be a cotton textile containing up to 100% cotton. In other embodiments, the second textile layer may be a wool textile containing up to 100% wool.

[0018] In yet another embodiment, the second textile layer may include a mixture of nylon and cotton, for example, a mixture in the range of 30% to 70% nylon and 30% to 70% cotton, or a mixture in the range of 40% to 60% nylon and 40% to 60% cotton, or a mixture in the range of 30% to 68% nylon and 30% to 68% cotton, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile.

[0019] In another embodiment, the second textile layer may include a mixture of polyester and cotton, for example, a mixture in the range of 30% to 70% polyester and 30% to 70% cotton, or 30% to 68% polyester and 30% to 68% cotton, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile.

[0020] In another embodiment, the second textile layer may include a mixture of aramid and flame-retardant viscose, for example, a mixture in the range of 30% to 68% aramid and 30% to 68% flame-retardant viscose, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile.

[0021] In any of the above embodiments, layers a) and c) are joined to each other using a first thermally reactive material layer, and layers c) and e) are joined to each other using a second thermally reactive material layer.

[0022] In any of the embodiments described above, the first heat-reactive material layer covers 25% or more of the first textile layer and / or carrier layer.

[0023] In any of the embodiments described above, the second heat-reactive material layer covers 25% or more of the second textile layer and / or carrier layer.

[0024] In any of the above embodiments, the carrier layer comprises porous polyethylene. In some embodiments, the carrier layer may be a film or membrane. In any of the above embodiments, the porous polyethylene is expanded ultra-high molecular weight polyethylene. In other embodiments, the porous polyethylene is a porous polymer containing pores, the pores being filled at least partially with a hydrophilic polymer. In some embodiments, the hydrophilic polymer is polyurethane, polyamide, polyester, polyether, ionomer, or a copolymer or combination thereof. In some embodiments, the porous polyethylene has a weight-average molecular weight greater than 500,000 grams / mol.

[0025] In any of the embodiments described above, the laminate further comprises one or more additional heat-reactive material layers and one or more additional textile layers, each subsequent additional layer being positioned adjacent to at least one of the first textile layer and / or the second textile layer.

[0026] In all of the above embodiments, the polymer resin includes an aqueous acrylic resin.

[0027] In any of the embodiments described above, the laminate further includes a protective layer. In embodiments including a protective layer, the protective layer is positioned between the first textile layer and the carrier layer.

[0028] This disclosure is, i) Adhering the first textile layer to the carrier layer with the first heat-reactive material in between to form a precursor laminate, and ii) Adhering the precursor laminate to the second textile layer with a second heat-reactive material in between, The present invention also relates to a method for forming a laminate, wherein the first and second heat-reactive materials each comprise a polymer resin and an expandable graphite, and the carrier layer comprises porous polyethylene.

[0029] In any of the embodiments described above, the laminate can be used for protective articles, and the first textile layer is the outer part of the protective article compared to a second textile layer that forms the inner part of the protective article. Examples of protective articles include clothing such as shirts, jackets, pants, jumpsuits, overalls, aprons, hats, gloves, and footwear, as well as covers, blankets, and tents.

[0030] This disclosure also relates to the use of any of the aforementioned laminates to improve the thermal protection performance of a protective article containing a laminate against arc discharge, compared to a protective article that does not use the first and second thermally reactive material layers.

[0031] This disclosure relates to garments including a laminate of any of the embodiments described above.

[0032] The laminates according to this disclosure are useful for use as flame-retardant articles such as flame-retardant clothing, flame-retardant blankets, or flame-retardant covers. Typically, the manufacture of flame-retardant clothing required the use of flame-retardant textiles. The laminates described herein enable their use for manufacturing laminates of non-flammable textiles and films. This use of non-flammable textiles can provide laminates that have one or more of the following advantages: Significant weight reduction, improved feel, enhanced breathability, increased durability, wide color range, superior moisture management, mechanical strength, and environmental friendliness are possible. Furthermore, the laminates disclosed herein can help reduce environmental impact by using recycled components in the textile layer. [Brief explanation of the drawing]

[0033] [Figure 1] Figure 1 is a schematic cross-sectional view of an embodiment described herein.

[0034] [Figure 2] Figure 2 is a schematic cross-sectional view of an embodiment described herein.

[0035] [Figure 3] Figures 3A and 3B are schematic diagrams of arrangements of thermally reactive materials according to two different embodiments.

[0036] [Figure 4] Figure 4 is a schematic diagram showing the states in which dots of a thermally reactive material overlap, partially overlap, and do not overlap. [Modes for carrying out the invention]

[0037] All disclosures of cited patent and non-patent documents are incorporated herein by reference in their entirety.

[0038] As used herein, the terms “embodiments” or “disclosure” are not intended to be restrictive and apply generally to any embodiments specified in the claims or described herein. These terms are used interchangeably herein.

[0039] Unless otherwise disclosed, the terms “a” and “an” as used herein are intended to encompass one or more (i.e., at least one) of the features being referenced.

[0040] The features and advantages of this disclosure will be more readily understood by those skilled in the art by reading the following detailed description. For clarification, please understand that certain features of this disclosure described above and below in the context of individual embodiments may also be provided in combination as a single element. Conversely, various features of the disclosure described in the context of a single embodiment for the sake of brevity may also be provided individually or in any subcombination. Also, unless otherwise specified in the context, singular references may include plurals (for example, "a" and "an" may refer to one or more).

[0041] The use of numerical values ​​within the various ranges specified herein is, unless otherwise specified, indicated as an approximation, as if the minimum and maximum values ​​within the stated ranges were preceded by the word "approximately." In this way, even if there are slight variations above or below the stated ranges, they can be used to obtain substantially the same results as values ​​within those ranges. Furthermore, the disclosure of these ranges is intended to be a continuous range encompassing all values ​​between the minimum and maximum values.

[0042] As used herein, the terms “fiber,” “filament,” and “yarn” are interchangeable unless otherwise specified. “Fiber” is intended to mean a fine thread having a finite length, for example, a few millimeters to about 30 centimeters. “Filament” is intended to mean a fine thread having an essentially infinite length. A filament can be several thousand meters long. “Yarn” means a continuous strand containing one or more fibers and / or filaments. Any known yarn can be used, for example, single-ply yarn, twisted yarn, cord yarn, stretch yarn, or any combination thereof. Fibers and / or filaments can be used in the manufacture of yarn.

[0043] As used herein, the term “membrane” means a polymer in the form of an essentially two-dimensional sheet, where the length and width are much greater than the thickness, for example, both the length and width being at least 100 times the thickness. In some embodiments, the membrane is a porous membrane, having a pore structure such that, for example, water vapor can pass through the thickness of the membrane, but liquid water cannot permeate from one side of the membrane to the other. On average, the pore size is in the range of a few nanometers to about 1 micrometer.

[0044] As used herein, the term “film” means a porous membrane having a pore structure, wherein the pores are at least partially filled with a polymer so as not to allow gas or liquid flow through the opening pore channels of the membrane. In some embodiments, the polymer at least partially filling the pores may be a hydrophilic polymer.

[0045] The term "hydrophilic polymer" refers to a polymer that allows a substantial amount of moisture to pass through a film by absorbing moisture on one side of the film where the moisture concentration is high, and desorbing or evaporating moisture on the opposite side of the film where the water vapor concentration is low. In some embodiments, a hydrophilic polymer layer with a thickness of 10 micrometers has a moisture content of 5,000 g / m². 2 / day or more, or 10,000g / m² 2 It can have a water vapor permeation rate of more than / day.

[0046] Throughout this specification, the terms “porous polyethylene membrane,” “microporous polyethylene membrane,” and “polyethylene membrane” are used interchangeably. Unless otherwise specified, the above terms mean a polyethylene membrane having pores, characterized by i) a weight-average molecular weight exceeding 500,000 g / mol, ii) a porosity of at least 40%, and iii) a Gurley number of less than 200 sec.

[0047] Under magnification, the porous polyethylene membrane exhibits a fibril structure of polyethylene fibrils. At sufficient magnification, one or more polyethylene fibrils can be identified, and in some cases, three or more fibrils may be interconnected by one or more intersections of these fibrils.

[0048] As used herein, the term "polyethylene" means a polyethylene polymer containing one or more comonomers in less than 5% by mass. In some embodiments, the polyethylene does not contain fluorine-containing comonomers, and in yet another embodiment, the polyethylene is a polyethylene homopolymer.

[0049] As used herein, the term “meltable” means, when used in relation to fibers, filaments, yarns, or textiles, a fiber that melts at 280°C or below or 300°C or below, according to the melting and thermal stability tests described herein. In embodiments where the yarn or textile is made from a single material, for example 100% nylon, the melting point of the material is the melting point of nylon. However, in embodiments of yarns or textiles containing a mixture of both meltable and non-meltable fibers, the presence of the non-meltable component may mask the melting of the meltable material. For example, in the case of a textile containing a 50 / 50 blend of nylon 6.6 and cotton, the molten nylon 6.6 may be absorbed by the cotton component, and the textile sample may appear non-meltable when subjected to the melting and thermal stability tests described herein. Therefore, for the purposes of this disclosure, when meltable fibers are present in a mixture of meltable and non-meltable fibers, the mixture material will be considered a meltable material.

[0050] This disclosure describes textiles used in various layers of laminates. When used herein, each of the first and second textile layers may independently be a single-layer or multi-layer textile layer in the form of a woven, knitted, or nonwoven fabric. Textiles are manufactured from fibers, filaments, and / or yarns that are meltable, non-meltable, or a combination thereof. Fibers, filaments, or yarns may be synthetic and / or natural. Depending on the type and composition of the fibers, filaments, or yarns, the corresponding fibers may have a variety of properties. Textiles may be meltable, non-meltable, flammable, flame-retardant, abrasion-resistant, heat-resistant, shrink-resistant, or a combination of these properties.

[0051] As used herein, the term “shrinkage resistance” means that the textile and / or laminate shrinks by less than 20%, less than 10%, or less than 5% in width, length, or both, when exposed to a high-energy event. In other embodiments, the laminates described herein shrink by less than 20%, less than 10%, or less than 5% when subjected to a shrinkage test at 180°C according to ISO 17493. In other embodiments, the laminates described herein shrink by less than 20%, less than 10%, or less than 5% when subjected to a shrinkage test at 260°C according to ISO 17493. As used herein, the terms “high energy” or “high-energy event” mean exposure to a temperature of 180°C or higher for 0.1 seconds or more.

[0052] This specification describes a laminate having a) a first textile layer, b) a first heat-reactive material layer, c) a carrier layer containing porous polyethylene, d) a second heat-reactive material layer, and e) a second textile layer, wherein the first and second heat-reactive material layers each independently contain a polymer resin and an expandable graphite, the first heat-reactive material layer is located between the first textile layer and the carrier layer, and the second heat-reactive material layer is located between the carrier layer and the second textile layer. This laminate can be used to manufacture protective articles, including protective clothing, where the first textile layer is typically the outermost layer of the garment and the second textile layer is the inner layer. Examples of protective articles include clothing, garments, tents, blankets, and / or covers. Examples of protective clothing include jackets, trousers, shirts, vests, overalls, as well as gloves, gaiters, hoods, footwear, and shoes. Protective clothing containing the laminate can be waterproof or water-resistant and breathable. Protective clothing needs to be lightweight for widespread use, especially in situations where there is a risk of exposure to flash fires or high-temperature events, such as exposure to electric arc flashes, but the probability of such occurrences is low.

[0053] In some embodiments, the laminate has a weight of, for example, 500 grams / meter 2 The weight can be less than or equal to (gsm). In some embodiments, the laminate can have a weight in the range of 200gsm to 500gsm, or 200gsm to 475gsm, or 200gsm to 450gsm, or 200gsm to 425gsm, or 200gsm to 400gsm. In yet another embodiment, the laminate can have a weight in the range of 225gsm to 400gsm, or 250gsm to 375gsm, or 275gsm to 375gsm, or 275gsm to 350gsm.

[0054] To reduce the weight of a laminate, it is necessary to reduce the weight without compromising its protective properties or reducing its breathability or waterproofness. As described herein, the weight of each of the first textile layer, the carrier layer, and the second textile layer can be reduced without compromising the laminate's ability to protect the wearer from exposure to high-temperature events or arc flashes. The overall weight of the laminate can be reduced by using relatively lightweight layers. However, if the weight of layers a), c), and / or e) is too low, there is a risk that the heat or energy from an event may affect the wearer in the event of a flash fire or other high-temperature conditions. Therefore, the laminate of the present invention provides further protection by using at least two layers of heat-reactive material. The first heat-reactive material layer can absorb at least a portion of the heat from the event, and the second heat-reactive material layer can absorb any additional heat that may have been transferred through the carrier layer, helping to minimize the heat transferred to the wearer.

[0055] First textile layer

[0056] The laminate described herein includes a first textile layer. Suitable fibers, filaments, or yarns for the first textile layer may include nylon, nylon 6, nylon 6.6, nylon 12, nylon 6.12, polyester, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyurethane, elastane, acrylic, polyolefin, polyethylene, polypropylene, aramid, meta-aramid, para-aramid, NOMEX® aramid, KEVLAR® aramid, polyamide-imide, polybenzimidazole (PBI), polybenzoxazole (PBO), flame-retardant viscose, flame-retardant cotton, modacryl, polyamine, carbon fiber, glass fiber, polyacrylonitrile (PAN), PTFE, viscose, rayon, cotton, wool, silk, cellulose, jute, flax, bamboo, hemp, or combinations thereof. Virgin fibers or regenerated fibers or combinations thereof, filaments, or yarns may be used. Fibers and / or filaments can be combined using known methods to form yarn. Yarn may be produced from a single type of fiber or filament, or from a mixture of two or more different types of fibers or filaments. Similarly, the first textile layer can be formed from a single type of fiber, filament, and / or yarn, and / or from multiple different fibers, filaments, and / or yarn, to possess desired textile properties. The textile may be a woven, knitted, or nonwoven textile.

[0057] The first textile layer forms part of a laminate intended to be the outer layer of a protective article that is directly exposed to high-energy events such as heat and / or flame. In some embodiments, the first textile layer includes a fusible textile layer, i.e., a textile layer containing fusible fibers as defined herein. In some embodiments, the first textile layer includes a non-fusible textile layer, e.g., a cotton textile. In other embodiments, the first textile layer may include a combination of fusible and non-fusible fibers, filaments and / or yarns, e.g., a nylon / cotton blend or a polyester / cotton blend. In some embodiments, the first textile is a non-fusible and / or non-dripping textile according to fusion and thermal stability tests as defined herein. In some embodiments, the first textile is a textile containing fusible fibers, filaments or yarns, and is considered a non-fusible and / or non-dripping textile according to fusion and thermal stability tests as defined herein. In yet another embodiment, the first textile layer may include a combination of meltable fibers, filaments and / or yarns and flame-retardant non-meltable fibers, filaments and / or yarns. For example, the first textile layer may be a woven textile in which flame-retardant filaments or yarns are arranged in a regular repeating pattern in the warp and / or weft directions, for example, for every n warp and / or weft courses, where each n is independently 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20, and the remaining filaments or yarns are meltable. Arranging flame-retardant filaments or yarns every n courses is similar to that of a ripstop woven textile.Suitable textile layers containing both meltable fibers and flame-retardant non-meltable fibers are described in International Patent Application Publication WO2019 / 212549 or U.S. Patent Application Publication 2022 / 0363042 by WL Gore and Associates, Inc., the contents of which are incorporated herein by reference in their entirety.

[0058] In any of the embodiments described above, the first textile layer may contain fusible fibers in a range of 0% to 100%, based on the total mass of fusible and non-fusible fibers in the first textile layer. In other embodiments, the first textile layer may contain more than 0% to 100% meltable fibers, or 0.5% to 100% meltable fibers, or 1% to 100% meltable fibers, or 1% to 99% meltable fibers, or 3% to 100% meltable fibers, or 5% to 100% meltable fibers, or 10% to 100% meltable fibers, or 20% to 100% meltable fibers, or 25% to 100% meltable fibers, or 30% to 100% meltable fibers, or 35% to 100% meltable fibers, or 40% to 100% meltable fibers, or 50% to 100% meltable fibers, or 60% to 100% meltable fibers, or 70% to 100% meltable fibers, or 80% to 100% meltable fibers, or 90% to 100% meltable fibers. In other embodiments, the first textile comprises a combination of meltable and non-meltable fibers, with non-meltable fibers ranging from 1% to 99% and meltable fibers ranging from 1% to 99%, where the mass percentage is based on the total mass of fibers in the first textile layer. Each percentage is based on the total mass of fibers in the first textile layer.

[0059] In some embodiments described above, the first textile layer may include a 100% nylon textile. In some embodiments described above, the first textile layer may be a 100% polyester textile. In other embodiments, the first textile layer may be a cotton textile containing up to 100% cotton. In other embodiments, the first textile layer may be a wool textile containing up to 100% wool.

[0060] In yet another embodiment, the first textile layer may contain a mixture of nylon and cotton, for example, a mixture in the range of 30% to 70% nylon and 30% to 70% cotton, or a mixture in the range of 30% to 68% nylon and 30% to 68% cotton, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile.

[0061] In a further embodiment, the first textile layer may include a mixture of polyester and cotton, for example, a mixture in the range of 30% to 70% polyester and 30% to 70% cotton, or a mixture in the range of 30% to 68% polyester and 30% to 68% cotton, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile.

[0062] In yet another embodiment, the laminate includes a first textile layer containing a combination of meltable and non-meltable fibers in the range of 1% to 99% non-meltable fibers and 1% to 99% meltable fibers. In other embodiments, the first textile layer may contain meltable fibers in the range of 5% to 100%, or 10% to 100%, or 20% to 100%, or 25% to 100%, or 30% to 100%, or 35% to 100%, or 40% to 100%, or 50% to 100%, or 60% to 100%, or 70% to 100%, or 80% to 100%, or 90% to 100%. Each of these percentages is based on the total mass of meltable and non-meltable fibers in the first textile layer.

[0063] In further embodiments, the first textile layer may be a knitted fabric, such as a nylon knitted fabric, a polyester knitted fabric, a polyurethane knitted fabric, or a knitted fabric comprising one or more combinations of nylon, polyester, cotton and / or polyurethane. The knitted structure can provide a relatively lightweight textile that helps reduce the overall weight of the laminate while still maintaining the desired flame retardancy and / or arc resistance of the laminate. In some embodiments, the laminate includes a first textile layer that does not contain, or is essentially free of, flame retardants or fire-resistant additives. In some embodiments, the first textile layer may be made from one or more recycled fibers, filaments or textiles.

[0064] In some embodiments, the first textile layer includes a textile manufactured from fibers, filaments, or yarns with denier (weight in grams per 9,000 meters of fiber, filament, or yarn) ranging from 5 denier (D) to 400D. In other embodiments, the fibers, filaments, or yarns may have denier ranging from 5D to 300D, or 5D to 250D, or 5D to 200D, or 7D to 150D, or 7D to 100D.

[0065] In some embodiments, the first textile layer may be a woven or knitted textile comprising nylon fibers, filaments, or yarns having deniers in the range of 5D to 400D. In some embodiments, the first textile layer includes a woven or knitted textile made from nylon yarns having deniers of 5D to 400D, or 5D to 300D, or 5D to 250D, or 5D to 200D, or 7D to 150D, or 7D to 100D. In other embodiments, the first textile layer may be a woven or knitted textile made from polyester fibers, filaments, or yarns, the yarns having deniers in the range of 5D to 400D, or 5D to 300D, or 5D to 250D, or 5D to 200D, or 7D to 150D, or 7D to 100D. Depending on the circumstances, the first textile layer described herein may be waterproof, and / or the first textile layer or laminate may be made water-resistant by applying a durable water-repellent (DWR) treatment to the first textile layer. This DWR coating may be on the outer surface of the first textile layer, i.e., the surface opposite to the first heat-reactive material layer. In another embodiment, the first textile layer comprises a waterproof material.

[0066] The first textile layer may also contain an antistatic agent, antistatic particles, antistatic fibers, or antistatic polymer as a filler, a coating agent, or as part of the fibers constituting the first textile layer. Suitable antistatic materials may include, for example, carbon black, conductive fibers, metal particles, or conductive polymers.

[0067] The first textile layer is lightweight, weighing 200 grams / square meter (gsm) or less, for example, less than 200gsm, less than 190gsm, less than 180gsm, less than 170gsm, less than 160gsm, less than 150gsm, less than 140gsm, less than 130gsm, less than 125gsm, less than 120gsm, less than 110gsm, less than 100gsm, less than 90gsm, or less than 85gsm. For the first textile layer to have sufficient strength and durability, the textile weight should be 15gsm or more, 20gsm or more, 25gsm or more, 30gsm or more, 35gsm or more, 40gsm or more, 45gsm or more, 20gsm or more, or 55gsm or more. It should be noted that as the amount of non-meltable fibers increases, the textile weight generally needs to be increased to obtain a first textile layer with sufficient durability, strength, and abrasion resistance. For example, in the case of a 50 / 50 nylon / cotton blend, the textile weight should be in the range of 120-150 gsm.

[0068] In another embodiment, the laminate may further include a protective layer comprising a scrim layer or an open textile layer. The protective layer is an intermediate layer between the first textile layer and the carrier layer and is made of a flame-retardant material. As used herein, scrim is intended to mean a woven textile in which the average gap between adjacent warp and / or weft filaments or yarns is in the range of 0.50 mm to 10 mm. As used herein, open textile is defined as having an average opening area between adjacent filament or yarn courses of 0.25 mm, determined by measuring 4 to 6 openings by optical profilometry using a Keyence VR-5000 wide-area 3D measurement system controller and integrated software, and calculating the average of those measurements. 2 ~100 mm 2 This is intended to mean knitted or nonwoven textiles within this range. Protective textiles should be relatively thin, with a thickness of 0.002 mm to 0.5 mm.

[0069] A relatively open and thin protective layer allows the heat-reactive material to adhere both the primary textile layer and the protective layer to the carrier layer. When exposed to heat, the heat-reactive material is thought to expand in the open areas of the protective layer, i.e., the spaces between the filaments or yarns, and absorb the melting primary textile layer. Therefore, the thicker the protective layer, the larger the average open area between adjacent warp and / or weft threads in the scrim, or the larger the open area of ​​the knitted or nonwoven textile needs to be.

[0070] The protective layer may include naturally flame-retardant fibers or fibers treated with flame retardants. Examples of naturally flame-retardant fibers include aramid fibers, meta-aramid fibers, para-aramid fibers, polyamide-imide fibers, polybenzimidazole (PBI) fibers, polybenzoxazole (PBO) fibers, flame-retardant viscose fibers, flame-retardant cotton fibers, modacryl fibers, polyamine fibers, carbon fibers, glass fibers, polyacrylonitrile (PAN) fibers, alumina silica fibers, BELCOTEX® silica gel fibers, ceramic fibers, calcium magnesium silicate fibers, basalt fibers, novoroid / phenol fibers, PTFE fibers, or combinations thereof. In some embodiments, the naturally flame-retardant fibers are aramid fibers, glass fibers, or combinations thereof. Materials that are not inherently flame-retardant but can be treated with flame retardants include, for example, nylon, nylon 6, nylon 6.6, nylon 12, nylon 6.12, polyester, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyurethane, elastane, acrylic, polyolefin, polyethylene, polypropylene, or combinations thereof. These materials can be processed into fibers, filaments, or yarns, and into fabrics produced from them.

[0071] The use of a protective layer between the first textile layer and the carrier layer can help the laminate pass the fracture evaluation when tested in the ISO 15025 A / B horizontal combustion test. In other words, a laminate including a protective layer will not fracture when tested in the ISO 15025 A / B horizontal combustion test.

[0072] Thermally reactive materials

[0073] The laminates described herein also include a first thermally reactive material layer and a second thermally reactive material layer. The first thermally reactive material and the second thermally reactive material layer can be selected independently and may be the same or different. For the purposes of this disclosure, unless otherwise specified, the following descriptions of thermally reactive materials are intended to describe materials that can be used for the first thermally reactive material layer and / or the second thermally reactive material layer.

[0074] The laminates described herein comprise at least two layers of heat-reactive material. Each layer of heat-reactive material independently comprises a mixture of a polymer resin and graphite, such as expandable graphite. Expandable graphite suitable for use in protective articles, when tested using the furnace expansion test described herein, has an average expansion coefficient of at least 9 cc / g at 300°C. For example, Asbury 3626 expandable graphite (available from Asbury Graphite Mills, Inc.) has an average expansion coefficient of approximately 19 cc / g at 300°C when tested according to the furnace expansion test described herein, while Asbury 3538 expandable graphite (available from Asbury Graphite Mills, Inc.) has an average expansion coefficient of approximately 4 cc / g at 300°C.

[0075] A suitable expandable graphite expands by at least 300%, or at least 350%, or at least 400%, or at least 450%, or at least 500%, according to the TMA expansion test described herein. In some embodiments, the laminate comprises a thermally reactive material along with expandable graphite having an expansion of more than 900 micrometers (μm) at 280°C according to the TMA expansion test described herein.

[0076] In one embodiment, the heat-reactive material takes the form of a mixture of a polymer resin and expandable graphite. The particle size of the expandable graphite suitable for the present invention should be selected so that the heat-reactive material can be applied by a selected application method. For example, when the heat-reactive material is applied by gravure printing technology, the particle size of the expandable graphite should be small enough to fit into a gravure cell.

[0077] In certain embodiments, the thermally reactive material includes expandable graphite having at least the expandability described above and exhibiting an endothermy of at least about 100 joules / gram (J / g) when tested according to the differential scanning calorimetry (DSC) endothermy test method described herein. In other embodiments, it may be desirable to use expandable graphite exhibiting an endothermy of about 150 J / g or more, about 200 J / g or more, or about 250 J / g or more.

[0078] In some embodiments, laminates containing a thermally reactive material including expandable graphite with an expansion of more than 900 micrometers (μm) and an endothermic capacity of more than 100 J / g at 280°C exhibit an average afterflame time of less than 20 seconds, or an average char length of less than 20 centimeters (cm), or both, when tested according to the edge ignition test described herein.

[0079] In other embodiments, the laminate may have an average afterburn time of less than 10 seconds or less than 2 seconds and / or an average char length of less than 15 cm or less than 10 cm when tested according to an edge ignition test.

[0080] The first thermally reactive material layer and the second thermally reactive material layer each independently comprise a polymer resin and expandable graphite. Polymer resins having a melting temperature or softening temperature of less than 280°C (measured by DSC) are suitable for use in the thermally reactive material. In some embodiments, the polymer resin is sufficiently flowable or deformable such that the expandable graphite substantially expands upon thermal exposure at 280°C or lower. It may be desirable that the elongational viscosity of the polymer resin is sufficiently low to allow expansion of the expandable graphite, and sufficiently high to maintain the structural integrity of the thermally reactive material after expansion of the mixture of the polymer resin and the expandable graphite.

[0081] In other embodiments, the storage modulus at 200°C is 10 3 ~10 8 dynes / cm 2 , and a polymer resin having a tan δ of 0.1 to 10 is used. In other embodiments, the polymer resin has a storage modulus of 10 3 ~10 6 dynes / cm 2 . In another embodiment, a polymer resin having a storage modulus of 10 3 ~10 4 dynes / cm 2 is used.

[0082] Suitable polymer resins for use in some embodiments are elastomeric. Suitable polymer resins for use in some embodiments are crosslinkable, for example, crosslinkable polyurethane, MOR-MELT® R7001E (from Rohm & Haas). In other embodiments, suitable polymer resins are thermoplastic resins with a melting temperature of 50°C to 250°C, for example, DESMOMELT® VP KA 8702 (from Covestro AG, Leverkusen, Germany). Suitable polymer resins for use in the embodiments described herein include, but are not limited to, polymers comprising polyester, thermoplastic polyurethane and crosslinkable polyurethane and combinations thereof. Other polymer resins may include one or more polymers selected from polyester, polyamide, acrylic, vinyl polymer, polyolefin, silicone or epoxy.

[0083] In other embodiments, the polymer resin may be an aqueous polymer resin, such as an aqueous acrylic resin, like the acrylic resin taught in EP4030952, the details of which are incorporated herein in their entirety.

[0084] In some embodiments, the aqueous acrylic resin may be an aqueous acrylic polymer resin. The aqueous acrylic resin may contain acrylamide repeating units. The aqueous acrylic resin may contain N-methylolacrylamide repeating units. The aqueous acrylic resin is an aqueous acrylic polymer resin and may contain N-methylolacrylamide repeating units, for example, EDOLAN® AM, available from Tanatex Chemicals BV in Ede, Netherlands. The aqueous acrylic resin may be an acrylic copolymer containing different amounts of styrene. The aqueous acrylic resin may be an acrylic copolymer containing different amounts of acrylamide monomer. The aqueous acrylic resin may further contain acrylonitrile, vinyl acetate, styrene, or a combination thereof.

[0085] In some embodiments, the aqueous acrylic resin can be a thermoplastic resin. The aqueous acrylic resin can be self-crosslinking. The acrylic polymer can be a crosslinkable acrylic polymer. "Self-crosslinking" means that the aqueous acrylic resin contains functional groups that can react with each other to form a crosslinked polymer under specific conditions known in the art, such as high temperature or hydrolysis conditions. In some embodiments, self-crosslinking can be initiated without additional chemicals by applying a high temperature, for example, about 120°C or higher. The aqueous acrylic resin can contain a crosslinking agent. The aqueous acrylic resin does not need to be crosslinked. The aqueous acrylic resin can be self-crosslinking and can further contain a crosslinking agent. Additional crosslinking agents can improve adhesion to textiles. A heat-reactive composition can contain a crosslinking agent to form a crosslinked aqueous acrylic resin.

[0086] In some embodiments, the heat-reactive composition may comprise, or essentially consist of, an aqueous acrylic resin, an expandable graphite, at least one flame retardant, and a crosslinking agent. Suitable crosslinking agents include, for example, one or more polyisocyanate crosslinking agents and blocked polyisocyanate crosslinking agents. Other suitable crosslinking agents include the following materials: N-methoxymethylmelamine, methylolmelamine, carbodiimide, polycarbodiimide, isocyanate, polyisocyanate, diaminocarbamate, propyleneimine crosslinking agents, propyleneimine, aliphatic propyleneimine, aromatic propyleneimine derivatives, reaction products of polyfunctional acrylates and propyleneimine, (cyclic)aliphatic bisamide crosslinking agents, or combinations thereof, depending on their chemical structure.

[0087] In some embodiments, the thermoreactive composition may contain, based on the total mass of the aqueous acrylic resin and the crosslinking agent, about 10% by mass or less, or about 9% by mass or less, or about 8% by mass or less, or about 7% by mass or less, or about 6% by mass or less, or about 5% by mass or less, or about 4% by mass or less, or about 3% by mass or less, or about 2% by mass or less, or about 1% by mass or less of the crosslinking agent.

[0088] Aqueous acrylic resins with a melting or softening temperature of less than approximately 280°C can be used. As measured by TMA expansion tests, the aqueous acrylic resin can expand expandable graphite by at least approximately 900 micrometers when heated to approximately 280°C.

[0089] The heat-reactive material may include a flame-retardant material. In some embodiments, the flame-retardant material may be incorporated into the polymer resin. In some embodiments, the polymer resin may contain at least one component or additive selected from the group consisting of chlorine compounds, bromine compounds, antimony oxide, organophosphorus compounds, phosphate esters, resorcinol bis(diphenyl phosphate), zinc borate, ammonium polyphosphate, melamine cyanurate, melamine polyphosphate, molybdenum compounds, alumina trihydrate, and magnesium hydroxide. These components or additives can improve the flame retardancy of the composite article. In some embodiments, the flame-retardant material is melamine polyphosphate, resorcinol bis(diphenyl phosphate), or a combination thereof. The flame-retardant material may be present in an amount ranging from 0 to 60% by mass based on the total mass of the heat-reactive material. In other embodiments, the flame-retardant material may be present in an amount ranging from 10 to 55% by mass relative to the total mass of the heat-reactive material. In some embodiments, at least one of the first heat-reactive material layer or the second heat-reactive material layer contains the flame-retardant material.

[0090] In some embodiments, when the laminate is exposed to flame and / or extreme heat, for example, a temperature of 280°C or higher, any molten portions of the first textile layer, if present, melt and are absorbed by the heat-reactive material. Simultaneously, the heat-reactive material can expand. In other embodiments, when the laminate is exposed to flame and / or extreme heat, for example, a temperature of 300°C or higher, any molten portions of the first textile layer, if present, melt and are absorbed by the heat-reactive material. Simultaneously, the heat-reactive material can expand. These processes can also cause the formation of a carbide containing the first textile layer and the heat-reactive material.

[0091] The carbide produced by exposing the first textile layer and the first heat-reactive material layer to heat and / or high temperatures, for example, 280°C or above or 300°C or above, is a heterogeneous mixture of the first textile layer and the expanded first heat-reactive material layer. According to this specification, carbide is intended to refer to the carbonaceous material remaining after exposing the molten first textile layer and heat-reactive material to temperatures of 280°C or above or 300°C or above. The carbide is a mixture of expanded graphite, molten polymer resin, and either or both of the molten portions of the first textile layer. At temperatures of 280°C or above or 300°C or above, either or both of the first textile layer and the polymer resin may participate in oxidation or combustion processes, forming additional carbonaceous material that becomes part of the carbide. The formation of the carbide can help insulate the layer behind the carbide from heat exposure.

[0092] When the laminate is exposed to flame and / or extreme heat, the first heat-reactive material layer can expand (or mix) within the molten first textile layer. This allows the first heat-reactive material layer to mix with the molten first textile layer, protecting the underlying layer and the wearer of the article. In one embodiment, when tested according to the horizontal combustion test method described herein, the laminate can have a fracture time that is at least 20 seconds, or at least 30 seconds, longer than a laminate composed of substantially the same material but without the expandable graphite material, and in which the above expansion process does not occur.

[0093] In some embodiments of the heat-reactive material, a mixture of polymer resin and expandable graphite expands to form multiple tendril structures containing the expanded graphite. The total surface area of ​​the heat-reactive material increases significantly when compared to the same mixture before expansion. In one embodiment, the surface area of ​​the mixture increases by at least 5 times after expansion. In another embodiment, the surface area of ​​the mixture increases by at least 10 times after expansion. Furthermore, the tendril structures often extend outward from the expanded mixture. In embodiments where the heat-reactive material is arranged discontinuously on a substrate, the tendril structures extend to at least partially fill the openings between the discontinuous regions. In yet another embodiment, the tendril structures are elongated, with a length-to-width aspect ratio of at least 5:1.

[0094] For example, when exposed to high-energy events such as heat, flames, and / or arc flashes, the combination of the first textile layer and the first heat-reactive material layer can dissipate or absorb at least a portion of the incident energy transmitted during the high-energy event through the melting and / or expansion described above. When the energy and / or heat transmitted through the carrier layer is sufficiently high, the expandable graphite particles of the second heat-reactive material layer expand similarly to the expandable graphite of the first heat-reactive material layer, forming an additional insulating layer to absorb another portion of the energy from the high-energy event and improve the level of thermal protection for the wearer. In some embodiments, the second textile layer may include meltable fibers, filaments, and / or yarns. If the second textile layer also melts, the second heat-reactive material layer can absorb the melting second textile layer, minimizing damage to the wearer.

[0095] In several embodiments, the thermally reactive material can be produced by a method of uniformly mixing a polymer resin and expandable graphite without causing substantial expansion of the expandable graphite. Suitable mixing methods include, but are not limited to, paddle mixers, blending, and other low-shear mixing techniques. In one method, uniform mixing of the polymer resin and expandable graphite particles is achieved by mixing the monomer or prepolymer with the expandable graphite before polymerization of the polymer resin. In another method, the expandable graphite is mixed with a molten polymer, and the solvent is removed after mixing. In yet another method, the expandable graphite is mixed with a hot-melt polymer at a temperature lower than the expansion temperature of the expandable graphite and higher than the melting temperature of the polymer. In a method of achieving uniform mixing of the polymer resin and expandable graphite particles or expandable graphite aggregates, the expandable graphite is coated or encapsulated with the polymer resin before the expandable graphite is expanded. In other embodiments, uniform mixing is achieved before applying the thermally reactive material to a substrate.

[0096] The heat-reactive material contains 50% by mass (wt%) or less, 40 wt% or less, or 30 wt% or less of expandable graphite relative to the total mass of the heat-reactive material, with the remainder being substantially polymer resin and flame retardant material. In other embodiments, the expandable graphite accounts for 20 wt% or less, 10 wt% or less, or 5 wt% or less of the heat-reactive material, with the remainder being substantially polymer resin and flame retardant material. Generally, 5 wt% to 50 wt% of expandable graphite is desirable based on the total mass of the heat-reactive material. In some embodiments, desirable flame retardancy can be obtained even with a further reduction in the amount of expandable graphite. A loading amount of about 1 wt% may be useful. Depending on the desired properties and the structure of the resulting laminate, other levels of expandable graphite may also be suitable for other embodiments. Other additives such as pigments, fillers, antimicrobial agents, processing aids, and stabilizers can also be added to the heat-reactive material. When these other additives are present, they are generally present in amounts of less than about 10% by mass relative to the total mass of the thermally reactive material.

[0097] The first and second heat-reactive material layers, more specifically the polymer resin, can function as adhesives for attaching or bonding one layer to an adjacent layer, for example. For instance, the first heat-reactive material layer can bond the first textile layer to a carrier layer, and the second heat-reactive material layer can bond the carrier layer to a second textile layer. The first and second heat-reactive material layers can independently take the form of a discontinuous adhesive, such as a series of individual dots or shapes that do not touch or overlap each other. In other embodiments, the first and / or second heat-reactive material layers can be continuous layers extending over most of the length and / or width of the laminate. In yet another embodiment, the first and / or second heat-reactive material layers can take the form of a series of lines or grids extending over most of the length and / or width of the laminate. These lines or grids can be straight, curved, essentially parallel to each other, and / or overlap each other. When the first and / or second layers of thermally reactive material are applied discretely and discontinuously, the shape of the dots of thermally reactive material can be essentially arbitrary. In some embodiments, the shape can be a circle, ellipse, triangle, square, rectangle, star, polygon, quadrilateral, or other discrete shape. The shape of the first layer of thermally reactive material can be selected independently of the shape of the second layer of thermally reactive material.

[0098] A certain amount of thermally reactive material should be applied to bond the first textile layer, carrier layer, and second textile layer of the laminate and to provide the desired protection from high-energy events. Typically, each of the first and second thermally reactive material layers should contain at least 20 grams / meter 2It is applied to become a thermally reactive material of (gsm). In some embodiments, the amount of the first thermally reactive material layer and the second thermally reactive material layer can independently range from 20 gsm to about 130 gsm. In other embodiments, the amount of the first thermally reactive material layer and the second thermally reactive material can independently range from 30 gsm to 120 gsm, or 40 gsm to 110 gsm, or 50 gsm to 110 gsm, or 60 gsm to 110 gsm, or 70 gsm to 110 gsm.

[0099] Career level

[0100] This laminate includes a carrier layer positioned between a first thermally reactive material layer and a second thermally reactive material layer. The carrier layer can impart strength and durability to the laminate before one or more layers of thermally reactive material are exposed to high-energy events that cause expansion. The carrier layer may include polyethylene. Prior art laminates containing the disclosed thermally reactive material have used laminates in which a heat-resistant or thermally stable layer is laminated to a molten layer in order to impart strength after exposure to high-energy events, i.e., the thermally stable layer maintains structural integrity even after exposure to high-energy events. It is surprising that a laminate containing a layer that is a molten material or a layer considered to be a non-thermally stable layer can be used in the disclosed laminate and still retain at least some of the thermal protection properties required for a laminate exposed to high-energy events.

[0101] In some embodiments, the carrier layer may include a polyethylene membrane. The polyethylene membrane may be a waterproof and breathable polyethylene membrane having a porous structure. The porous polyethylene membrane includes a fibrillated structure of polyethylene fibrils, and at sufficient magnification, it can be confirmed that one or more polyethylene fibrils, and possibly three or more fibrils, can be interconnected by one or more intersections of three or more fibrils. It should be noted that a porous film having a fibril structure is different from a textile. In some embodiments, the carrier layer does not contain or is essentially flame retardant or fire retardant. In other embodiments, the carrier layer may be a porous film having pores filled at least partially with polymer. In yet another embodiment, the polymer filling at least part of the pores includes a flame retardant additive.

[0102] A suitable polyethylene membrane may a) contain 30% by mass or more of porous polyethylene with a weight-average molecular weight exceeding 500,000 g / mol (g / mol), where the mass percentage is based on the total mass of the porous polyethylene, b) have a porosity of at least 40%, and c) have a Gurley number of less than 200 sec. In some embodiments, the porous polyethylene membrane contains 30% by mass or more of polyethylene with a weight-average molecular weight exceeding 750,000 g / mol. In yet another embodiment, the porous polyethylene membrane contains 30% by mass or more of polyethylene with a weight-average molecular weight of 1.0 × 10 6It contains polyethylene exceeding g / mol. In yet another embodiment, 40% by mass or more of polyethylene has a weight-average molecular weight exceeding 500,000 g / mol, or 50% by mass or more of polyethylene has a weight-average molecular weight exceeding 500,000 g / mol. All mass percentages are based on the total mass of the porous polyethylene membrane. In some embodiments, the porous polyethylene membrane has a weight-average molecular weight exceeding 750,000 g / mol. In yet another embodiment, the porous polyethylene has a weight-average molecular weight exceeding 1,000,000 g / mol. In yet another embodiment, the polyethylene membrane has a weight-average molecular weight exceeding 1,500,000 g / mol or exceeding 1,750,000 g / mol. In yet another embodiment, the polyethylene has a weight-average molecular weight exceeding 2,000,000 g / mol, 3,000,000 g / mol, 4,000,000 g / mol, 5,000,000 g / mol, or exceeding 6,000,000 g / mol, or exceeding 7,000,000 g / mol, or exceeding 8,000,000 g / mol.

[0103] A porous polyethylene membrane is a porous polyethylene membrane having a porosity of at least 40%. In some embodiments, the porosity of the porous polyethylene membrane can be at least 50%, or at least 60%, or at least 70%, or at least 80%. The porosity can be calculated using the porosity test described herein. The porous polyethylene membrane can also have a Gurley time of less than 200 seconds, or less than 100 seconds, or 90 seconds or less, or 80 seconds or less, or 70 seconds or less, or 60 seconds or less, or 50 seconds or less, or 40 seconds or less, or less than 10 seconds.

[0104] Porous polyethylene membranes can be relatively lightweight, for example, 10 grams / meter. 2 (gsm) or less. In other embodiments, the porous polyethylene membrane may have a weight of 9 gsm or less, or 8 gsm or less, or 7 gsm or less, or 6 gsm or less, or 5 gsm or less, or 4 gsm or less, or 3 gsm or less, or 2 gsm or less.

[0105] The polyethylene film may also contain a hydrophilic polymer that fills at least a portion of the pores of the porous polyethylene membrane. The phrase "fills at least a portion of the pores" means that the hydrophilic polymer is absorbed into the pores of the polyethylene membrane and fills the pores to such an extent that it can be determined that there is no airflow (Gurley number 1000 seconds or more) through the film region containing the hydrophilic polymer. In other words, the hydrophilic polymer is not merely a coating on the walls of the polyethylene membrane that define the pores. Although some voids may exist, the hydrophilic polymer is thought to form a continuous layer within the region of the porous polyethylene membrane to which the hydrophilic polymer is applied. In another embodiment, the hydrophilic polymer forms a voidless, or substantially voidless, continuous layer within the region of the porous polyethylene membrane to which the hydrophilic polymer is applied. In yet another embodiment, substantially all of the pores of the porous polyethylene membrane are filled with the hydrophilic polymer.

[0106] The polyethylene membrane has a first surface and a second surface. A hydrophilic polymer is applied to the first surface of the porous polyethylene membrane, and the hydrophilic polymer permeates into at least a portion of the pores to form a polyethylene film, thereby filling at least a portion of the pores of the polyethylene membrane. The first surface of the polyethylene membrane may include a cap layer of hydrophilic polymer on the outside of the membrane. There is essentially no upper limit to the cap layer or amount of hydrophilic polymer on the first surface of the porous polyethylene membrane. However, if the cap layer is too thick, the beneficial properties of the porous polyethylene membrane will not be realized, so the upper limit for the cap is about 50 micrometers. In some embodiments, the thickness of the hydrophilic polymer cap layer on the first surface of the polyethylene membrane can be 40 micrometers or less, or 30 micrometers or less, or 20 micrometers or less, or 15 micrometers or less. In some embodiments, the thickness of the hydrophilic polymer cap layer on the first surface of the polyethylene membrane can be about 10 micrometers or less. In other embodiments, the capping layer on the first surface of the polyethylene film has a thickness of 10 micrometers or less, or 8 micrometers or less, or 6 micrometers or less, or 4 micrometers or less, or 2 micrometers or less. In yet another embodiment, there is no capping layer of hydrophilic polymer on the first surface of the polyethylene film. The second surface of the polyethylene film may be essentially free of hydrophilic polymer on its surface, for example, there is no hydrophilic polymer more than 1 micrometer thick from the surface of the polyethylene film. In some embodiments, a thickness less than the total thickness of the porous polyethylene film is filled with hydrophilic polymer, for example, 90% or less of the thickness of the polyethylene film may be filled with hydrophilic polymer. However, this is subject to the condition that sufficient hydrophilic polymer is absorbed to provide a porous polyethylene film with a Gurley number of 1000 seconds or more. In other embodiments, almost the entire thickness of the porous polyethylene film is filled with hydrophilic polymer. As used herein, the phrase “essentially the entire thickness” means that at least 90% of the thickness of the porous polyethylene film is filled with hydrophilic polymer.In other embodiments, a hydrophilic polymer can be applied not only to the first surface of the polyethylene film but also to the second surface. The hydrophilic polymer applied to the second surface may be the same as or different from the hydrophilic polymer applied to the first surface. In yet another embodiment, the polyethylene film may be a composite film obtained by applying a sufficient amount of hydrophilic polymer to the surface of a first porous polyethylene film to form a cap layer, and then laminating a second porous polyethylene film, which may be the same as or different from the first porous polyethylene film, via the hydrophilic polymer cap layer. This results in a three-layer composite film in which two porous polyethylene films are bonded to each other and a hydrophilic polymer is used as a layer between the two porous polyethylene films. If desired, an additional layer(s) of hydrophilic polymer can be applied to one or both outer surfaces of the composite film.

[0107] In some embodiments, the hydrophilic polymer can be applied continuously to a porous polyethylene membrane, so that essentially 100 percent of the surface area of ​​the porous polyethylene membrane is covered with the hydrophilic polymer. When used in this context, the term “continuous” means that the entire width or nearly the entire width of the porous polyethylene membrane is coated with the hydrophilic polymer. It should be noted that in many coating processes, frames or dams at the edges prevent the edges of the material roll from being coated, and thus the entire width of the membrane from being coated. In other embodiments, the hydrophilic polymer can be applied discontinuously to a porous polyethylene membrane. When used in this context, the term “discontinuous” means that less than 100 percent of the surface area of ​​the porous polyethylene membrane is coated with the hydrophilic polymer, and that a portion of the non-edge region of the porous polyethylene membrane does not contain the hydrophilic polymer. For example, a hydrophilic polymer applied to a porous polyethylene membrane as a series of dots or as a grid of orthogonal lines is considered a discontinuous coating. The area percentage of a porous polyethylene film filled with a hydrophilic polymer can be in the range of 20% to 100%, or 30% to less than 100%, or 40% to less than 100%, or 50% to less than 100%, or 60% to less than 100%, or 70% to less than 100%, or 80% to less than 100%, or 90% to less than 100%. In other embodiments, the hydrophilic polymer can be applied in a manner that generates random or non-random patterns of dots, polygons, parallel lines, intersecting lines, straight lines, curves, or any combination thereof, in order to obtain a desired area coverage. If oil repellency is desired for such a film, it is desirable in certain embodiments to include an oil-repellent coating, as described separately herein.

[0108] In terms of weight ratio, the polyethylene film can have a ratio of 30.0 to 0.5 in the ratio of the weight of the hydrophilic polymer to the weight of the porous polyethylene film. In other embodiments, the weight ratio of the hydrophilic polymer to the polyethylene film can be 20.0, 15.0, 10.0, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.0, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, or any weight ratio between these values.

[0109] Suitable hydrophilic polymers include, for example, polyurethanes, polyamides, polyesters, polyethers, ionomers, or copolymers or combinations thereof. In another embodiment, 5,000 grams / meter 2 / day or more, or 10,000 grams / meter 2 / day or more, or 15,000 grams / meter 2 / day or more, or 20,000 grams / meter 2 More than / day, or 25,000 grams / meter 2 Almost any suitable hydrophilic polymer can be used, as long as it has a water vapor permeability rate of 1 / day or more. The hydrophilic polymer can be a thermoplastic polymer or a crosslinkable polymer. In some embodiments, the hydrophilic polymer is polyurethane, and in yet another embodiment, the polyurethane is crosslinked polyurethane. Suitable polyurethane polymers include, for example, polyester urethane, polyether urethane, or polyether polyester urethane.

[0110] In some embodiments where coloring is desired, color can be added, for example, by using a pigment-containing hydrophilic polymer to which a pigment or dye has been added to a hydrophilic polymer, thereby obtaining a film with the desired color. In other embodiments, the porous polyethylene film can be colored during the formation of the porous polyethylene membrane according to known methods, such as master batching. Thus, one or both of the porous polyethylene membrane and the hydrophilic membrane can be colored or left uncolored. When both the porous polyethylene and the hydrophilic polymer are colored, they can be colored to the same or similar shades, or the colors can be selected independently of each other. Known pigments or dyes can be used, including organic pigments and dyes, inorganic pigments or dyes, metals, metal oxides, carbon black, titanium dioxide, or combinations thereof.

[0111] After the addition of a hydrophilic polymer, polyethylene films containing both the porous polyethylene membrane and the hydrophilic polymer may, in certain embodiments, become undesirably stiff and noisy when bent. If these stiff and noisy films are used to create multilayer laminates, the laminates may also become undesirably stiff and noisy when incorporated, for example, into clothing. It has been found that heating the film containing the polyethylene membrane and the hydrophilic polymer at a temperature above the melting point of polyethylene for a sufficient amount of time, as detailed herein, results in a multilayer laminate that is more tactile and less noisy compared to multilayer laminates that have not undergone this heat treatment process. The required temperature for this heat treatment is at least 125°C. In other embodiments, the required temperature for the heat treatment is at least 130°C. In yet another embodiment, the temperature of the heat treatment process is at least 135°C, or at least 140°C, or at least 145°C, or at least 150°C, or at least 155°C, or at least 160°C, or at least 165°C, or at least 170°C, or at least 175°C. When heated at temperatures exceeding 200°C for a sufficient amount of time, depending on the choice of hydrophilic polymer, the hydrophilic polymer and / or polyethylene may begin to decompose. The time required for this heat treatment varies depending on the heating temperature and the method used for heating; for example, a heating temperature of 125°C may require a longer heating time than a heating temperature of 165°C. The minimum heating time required for a given film and heating process can be easily determined by those skilled in the art, provided the temperature is high enough to melt a portion of the polyethylene. In film regions where the polyethylene membrane structure is surrounded or enclosed by a hydrophilic polymer, when the polyethylene melts, no disintegration or coalescence of the polyethylene, nor macroscopic deformation of the polyethylene membrane, occurs, and the permeability of the film is remarkably maintained.

[0112] The resulting polyethylene film, comprising a porous polyethylene membrane and a hydrophilic polymer, has a water vapor transmission rate (MVTR) of 2500 grams / meter. 2 / day(g / m 2( / day) or more, and the weight is 30 grams / meter 2 It is less than, and in some cases, the girly time is 1000 seconds or more. For it to be breathable, that is, for water vapor to be transported from one side of the film to the other without liquid water passing through the film, the MVTR is 2500 g / m 2 It should be at least / day. In other embodiments, the film is 3000g / m² 2 / day or more, 3500g / m 2 / day or more, 4000g / m 2 / day or more, 4500g / m 2 / day or more, 5000g / m 2 / day or more, 5500g / m 2 / day or more, 6000g / m 2 / day or more, 6500g / m 2 / day or more, 7000g / m 2 / day or more, 7500g / m 2 / day or more, 8000g / m 2 / day or more, 8500g / m 2 / day or more, 9000g / m 2 / day or more, 9500g / m 2 / day or more or 10,000g / m² 2 It is possible to have an MVTR of more than / day.

[0113] In some embodiments, the carrier layer comprises a polyethylene film, wherein the polyethylene film is a porous polyethylene membrane in which at least a portion of the pores of the porous polyethylene membrane are filled with a hydrophilic polymer. Useful porous polyethylene films that can be used as carrier layers are described in International Patent Application Publication WO2020 / 028328 or WO2020 / 028331 by WL Gore and Associates, Inc., both of which are incorporated herein by reference in their entirety.

[0114] In some embodiments, as illustrated in Figure 1, the laminate (10) includes a first textile layer (20), two heat-reactive material layers (30) and (30'), a carrier layer (40), and a second textile layer (50).

[0115] The carrier layer may include antistatic agents, antistatic particles, antistatic polymers, or antistatic fibers as fillers or coatings. Suitable antistatic agents, particles, or polymers may include, for example, carbon black, conductive fibers, metal particles, or conductive polymers.

[0116] The second textile layer

[0117] The laminate includes a second textile layer adjacent to a second heat-reactive material layer opposite the carrier layer. The second textile layer forms one of the outer layers of the laminate and is located opposite the first textile layer. Thus, the laminate has two "outer layers," the first textile layer and the second textile layer, and the two heat-reactive material layers and the carrier layer form the "inner layers" of the laminate. When the laminate is processed into an article, such as clothing, the first textile layer is intended to be the outer layer of the garment, and the second textile layer is intended to be the inner layer of the garment. However, since this laminate is a three-layer laminate in which an adhesive layer (the first heat-reactive material layer and the second heat-reactive material layer) bonds the three layers (the first textile layer, the carrier layer, and the second textile layer), in certain embodiments, the second textile layer can be used as the outer layer of the garment and the first textile layer as the inner layer.

[0118] The second textile layer can be a single-layer or multi-layer textile commonly used in the textile industry. Suitable fibers, filaments, or yarns may include nylon, nylon 6, nylon 6.6, nylon 12, nylon 6.12, polyester, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyurethane, elastane, acrylic, polyolefin, polyethylene, polypropylene, aramid, meta-aramid, para-aramid, NOMEX® aramid, KEVLAR® aramid, TWARON® aramid, polyamide-imide, polybenzimidazole (PBI), polybenzoxazole (PBO), flame-retardant viscose, flame-retardant cotton, modacryl, polyamine, carbon fiber, fiberglass, polyacrylonitrile (PAN), PTFE, viscose, rayon, cotton, wool, silk, cellulose, jute, flax, bamboo, hemp, or combinations thereof. These fibers and / or filaments can be combined using known methods to form a yarn. The yarn may be made from a single type of fiber or filament, or from a blend of two or more different types of fibers or filaments. Similarly, the second textile layer may be formed from a single type of fiber, filament, and / or yarn, or from multiple different fibers, filaments, and / or yarns, to provide desired textile properties. The textile may be a woven, knitted, or nonwoven textile. In some embodiments, the second textile layer may be flame retardant or fire retardant-free, or essentially flame retardant-free.

[0119] In any of the above embodiments, the second textile layer may contain fused fibers in a range of 0% to 100%, based on the total mass of fused and non-fused fibers in the second textile layer. In other embodiments, the second textile layer may contain more than 0% to 100% meltable fibers, or 0.5% to 100% meltable fibers, or 1% to 100% meltable fibers, or 1% to 99% meltable fibers, or 3% to 100% meltable fibers, or 5% to 100% meltable fibers, or 10% to 100% meltable fibers, or 20% to 100% meltable fibers, or 25% to 100% meltable fibers, or 30% to 100% meltable fibers, or 35% to 100% meltable fibers, or 40% to 100% meltable fibers, or 50% to 100% meltable fibers, or 60% to 100% meltable fibers, or 70% to 100% meltable fibers, or 80% to 100% meltable fibers, or 90% to 100% meltable fibers. In other embodiments, the second textile layer includes a combination of fused and non-fused fibers in the range of 1% to 99% non-fused fibers and 1% to 99% fused fibers. Each percentage is based on the total mass of fibers in the second textile layer.

[0120] In some embodiments described above, the second textile layer may be a 100% nylon textile. In other embodiments, the second textile layer may be a 100% polyester textile. In other embodiments, the second textile layer may be a cotton textile containing up to 100% cotton. In other embodiments, the second textile layer may be a wool textile containing up to 100% wool. In yet another embodiment, the second textile layer may contain a mixture of nylon and cotton, for example, a mixture ranging from 30% to 70% nylon and 30% to 70% cotton, or 40% to 60% nylon and 40% to 60% cotton, or 30% to 68% nylon and 30% to 68% cotton, and an antistatic agent of about 5% by mass or less based on the total mass of the textile.

[0121] In another embodiment, the second textile layer may include a polyester-cotton mixture, for example, a mixture in the range of 30% to 70% polyester and 30% to 70% cotton, or a mixture in the range of 30% to 68% polyester and 30% to 68% cotton, and an antistatic agent in an amount of about 5% by mass or less based on the total mass of the textile. In some embodiments, the second textile layer may be a textile containing a polyester-cotton mixture, for example, a mixture in the range of 45% to 90% polyester and 10% to 55% cotton.

[0122] In another embodiment, the second textile layer may include a mixture of aramid and flame-retardant viscose, for example, a mixture in the range of 30% to 68% aramid and 30% to 68% flame-retardant viscose, and may contain an antistatic agent of about 5% by mass or less based on the total mass of the textile. In yet another embodiment, the second textile layer may include a mixture of polyamide-imide and viscose, for example, a mixture in the range of 40% to 60% polyamide-imide and 40% to 60% viscose, and 1% to 5% antistatic agent.

[0123] In other embodiments, the second textile layer may include a mixture of viscose and polyester, for example, a mixture in the range of 50% to 70% viscose and 30% to 50% polyester.

[0124] In some embodiments, the second textile layer may be a flame-retardant textile layer comprising one or more flame-retardant natural fibers or flame-retardant synthetic fibers or filaments. In other embodiments, the second textile layer may be a textile comprising meta-aramid or para-aramid, viscose, and nylon. In other embodiments, the second textile layer may be a meltable textile layer. In some embodiments, the first and second textile layers comprise a meltable textile layer. In some embodiments, the second textile is a textile that is non-meltable and / or non-dripping according to melt and thermal stability tests as specified herein. In some embodiments, the second textile is a textile comprising meltable fibers, filaments, or yarns and is considered non-meltable and / or non-dripping according to melt and thermal stability tests as specified herein.

[0125] In yet another embodiment, the laminate includes a second textile comprising a combination of meltable and non-meltable fibers in the range of 1-99% non-meltable fibers and 1-99% meltable fibers. In other embodiments, the second textile layer may include 5-100% meltable fibers, or 10-100% meltable fibers, or 20-100% meltable fibers, or 25-100% meltable fibers, or 30-100% meltable fibers, or 35-100% meltable fibers, or 40-100% meltable fibers, or 50-100% meltable fibers, or 60-100% meltable fibers, or 70-100% meltable fibers, or 80-100% meltable fibers, or 90-100% meltable fibers. Each percentage is based on the total mass of fibers in the second textile layer. In further embodiments, the second textile layer may be a knitted fabric, such as a nylon knitted fabric, a polyester knitted fabric, a polyurethane knitted fabric, or a knitted fabric comprising one or more nylon, polyester, and / or polyurethane combinations. The knitted fabric structure can provide a relatively lightweight textile that helps reduce the overall weight of the laminate while maintaining the desired flame retardancy and / or arc resistance of the laminate. In some embodiments, the laminate includes a second textile layer that is free from or essentially free from flame retardants or fire retardants. In some embodiments, the second textile layer may be made from one or more recycled fibers, filaments, or textiles.

[0126] The second textile layer may also include, as a filler or coating agent, an antistatic agent, antistatic particles, an antistatic polymer, or an antistatic fiber. Suitable antistatic agents, particles, or polymers may include, for example, carbon black, conductive fibers, metal particles, or conductive polymers. In some embodiments, the second textile layer may include meltable fibers and one or more antistatic agents.

[0127] In some embodiments, the second textile may be a knitted or woven textile comprising a blend of 20% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, wherein the textile weight is 80 grams / square meter (gsm) or more. In other embodiments, the second textile may be a knitted or woven textile comprising a blend of 20% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, with a textile weight of 90 gsm or more; or the second textile may be a knitted or woven textile comprising a blend of 20% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, with a textile weight of 100 gsm or more; or the second textile may be a knitted or woven textile comprising a blend of 20% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, with a textile weight of 110 gsm or more. In other embodiments, the second textile may be a knitted or woven textile comprising a blend of 23% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, with a textile weight of 90 gsm or more; or the second textile may be a knitted or woven textile comprising a blend of 23% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, with a textile weight of 100 gsm or more; or the second textile may be a knitted or woven textile comprising a blend of 23% or more aramid and one or more of viscose, flame-retardant viscose, polyester and / or nylon, with a textile weight of 110 gsm or more.

[0128] The second textile layer can be a woven, knitted, or nonwoven textile. In some embodiments, the second textile is a relatively lightweight textile made from one or more synthetic fibers, for example, a knitted fabric containing a cotton-polyester blend. In another embodiment, the second textile layer can be an inherently flame-retardant layer containing flame-retardant fibers or filaments. In one embodiment, the second textile layer can be a woven textile containing a blend of aramid, flame-retardant viscose, and an antistatic agent. The second textile layer is lightweight, weighing 200 grams per square meter (gsm) or less, for example, less than 200gsm, less than 190gsm, less than 180gsm, less than 170gsm, less than 160gsm, less than 150gsm, less than 140gsm, less than 130gsm, less than 125gsm, less than 120gsm, less than 110gsm, less than 100gsm, less than 90gsm, or less than 85gsm. For the second textile layer to have sufficient strength and durability, the textile weight should be 15gsm or more, or 20gsm or more, or 25gsm or more, or 30gsm or more, or 35gsm or more, or 40gsm or more, or 45gsm or more, or 50gsm or more, or 55gsm or more. It should be noted that as the amount of non-meltable fibers increases, the textile weight generally needs to be higher for the second textile layer to have sufficient durability, strength, and abrasion resistance. For example, in the case of a 50 / 50 nylon / cotton blend, the textile weight should be in the range of 120-150 gsm.

[0129] In some embodiments, as illustrated in Figure 1, the laminate (10) includes a first textile layer (20), two heat-reactive material layers (30) and (30'), a carrier layer (40), and a second textile layer (50). In further embodiments, as illustrated in Figure 2, the laminate (10) may include a first textile layer (20), a carrier layer (40) which may be a porous polyethylene layer (42), two heat-reactive material layers (30) and (30'), and a second textile layer (50). The carrier layer (40) includes a porous polyethylene layer (42, shown as a dark rectangle) and a hydrophilic layer (42, shown as a cross-hatch pattern) which may form a cap layer (45) on one side of the polyethylene layer. Figure 2 shows the cap layer oriented toward the second textile layer (50), but in other embodiments, the cap layer may be oriented toward the first textile layer (20). The polymer layer (44) may be waterproof, air-impermeable, or both. The polymer layer (44) may be polyurethane, or a polyurethane layer containing one or more flame retardants.

[0130] As described above, in some embodiments, the laminate (10) may also include a protective layer located between the first textile layer (20) and the carrier layer (40). In such embodiments, the protective layer can be located on both sides of the heat-reactive material layer (30) (for example, between the first textile layer (20) and the heat-reactive material layer (30), or between the heat-reactive material layer (30) and the carrier layer (40)). In such embodiments, as described above, the protective layer has a relatively open structure, so the heat-reactive material (30) can bond the first textile layer (20) to the carrier layer (40) via the material of the protective layer.

[0131] Additional layer

[0132] One or more additional layers may be bonded to the laminate (10), the additional layers being bonded to the first textile layer (20), the second textile layer (50), or both. When one or more additional layers are bonded to the first textile layer (20), the one or more additional layers are selected from the list of materials described as useful for the first textile layer (20). When one or more additional layers are bonded to the second textile layer (50), the one or more additional layers may be selected from the list of materials described as useful for the second textile layer (50). One or more additional layers may be bonded to the laminate using known laminating adhesives, using one or more additional layers of the heat-reactive materials (30 and 30') described herein, or by other conventional methods such as sewing, quilting, bonding, hook-and-loop fasteners, buttons, snaps, or combinations thereof.

[0133] For example, referring to Figures 1 and 2, in some embodiments, at least one additional layer of the heat-reactive material (30) and at least one additional textile layer comprising a material selected from a list of materials described as useful for the first textile layer (20) are applied to the first textile layer (20) by utilizing the additional layer of the heat-reactive material (30) to bond at least one additional textile layer to the first textile layer (20). Similarly, in some embodiments, at least one additional layer (30') of the heat-reactive material and at least one additional textile layer comprising a material selected from a list of materials described as useful for the second textile layer (50) are applied to the second textile layer (50) by utilizing the additional layer (30') of the heat-reactive material to bond at least one additional textile layer to the second textile layer (50). In embodiments including multiple additional layers, each subsequent additional layer is positioned adjacent to the textile layer. For example, in some embodiments, additional layers placed on the first textile layer (20) may include, in a layered order, the first textile layer (20), a first additional layer of heat-reactive material (30), a first additional textile layer, a second additional layer of heat-reactive material (30), a second additional textile layer, and so on.

[0134] Application of the first thermally reactive material layer and the second thermally reactive material layer

[0135] The first heat-reactive material layer may be applied to the carrier layer, the first textile layer, or both. The second heat-reactive material layer may be applied to the carrier layer (on the opposite side from the first heat-reactive material layer), the second textile layer, or both. In some embodiments, the first heat-reactive material layer and / or the second heat-reactive material layer may be applied as a continuous layer. However, in embodiments where improved breathability and / or improved feel and texture are desired, the first heat-reactive material layer and / or the second heat-reactive material layer may be applied discontinuously to form a heat-reactive material layer with a surface coverage of less than 100%. Discontinuous application with a surface coverage of less than 100% can take various forms, but are not limited to, dots, grids, lines, or combinations thereof. In embodiments with discontinuous coverage, the average distance between adjacent areas of the discontinuous pattern is less than 5 millimeters (mm), preferably less than 3.5 mm, 2.5 mm, 1.5 mm, or 0.5 mm. The average distance between adjacent areas can be measured by measuring the edge-to-edge distance between adjacent dots. In embodiments where properties such as tactile feel, breathability, and / or laminate weight are important, surface coverage rates of less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 40%, or less than 30% can be used. In some embodiments, the first heat-reactive material layer covers 25% or more of the surface of the first textile layer. In some embodiments, the second heat-reactive material layer covers 25% or more of the surface of the second textile layer. Coverage rates can be calculated by measuring the geometry of the gravure cell or screen printing mask, depending on the application method used. One method to achieve a coverage rate of less than 100% includes applying the heat-reactive material by printing the heat-reactive material onto the surface of the first textile layer or the carrier layer, for example, by gravure printing. Figures 3A and 3B show examples in which a heat-reactive material layer (330) is provided in a discontinuous pattern of dots (Figure 3A) and grids (Figure 3B) on a layer such as a first textile layer (320). Each individual layer of heat-reactive material can be applied in proportion such that the added weight of heat-reactive material is between 20 gsm and 120 gsm.In some embodiments, layers of heat-reactive material may be applied in proportions such that the added weight is less than 120 gsm, less than 100 gsm, less than 90 gsm, or less than 80 gsm. The added weight can be determined by weighing samples of the same size before and after the application of the heat-reactive material and normalizing the sample size to 1 square meter.

[0136] In some embodiments, the method for forming a laminate comprising a first textile layer, a carrier layer, a second textile layer, and two heat-reactive material layers can be carried out in a stepwise process, while in other embodiments, it can be carried out in a continuous process. In some embodiments, the stepwise process may include a step of forming a precursor laminate comprising a second textile layer, a carrier layer, and a second heat-reactive material layer that bonds the second textile layer and the carrier layer. In this stepwise process, the second heat-reactive material layer can be applied continuously or discontinuously to the second textile layer, the carrier layer, or both the second textile layer and the carrier layer. The second textile layer and the carrier layer can then be bonded using any known laminating technique, such as forming the precursor laminate using a calender roll. The precursor laminate can be used immediately or stored for minutes, days, or months until needed. After the formation of the precursor laminate, the first textile layer can be applied. In this process, the first heat-reactive material layer is applied continuously or discontinuously to the first textile layer, the carrier layer side of the precursor laminate, or both. Then, for example, two or more calender rolls can be used to bond the first textile layer to the precursor laminate (carrier layer side).

[0137] In other embodiments, the process of forming a laminate comprising a first textile layer, a carrier layer, a second textile layer, and two heat-reactive material layers can be carried out in a stepwise process, where the precursor laminate comprises the first textile layer, the first heat-reactive material layer, and the carrier layer. In these embodiments, the first heat-reactive material layer may be applied continuously or discontinuously to the first textile layer, the carrier layer, or both the first textile layer and the carrier layer. The precursor laminate can then be formed by bonding the first textile layer and the carrier layer using any known laminating technique, for example, using a calendering roll. The precursor laminate can be used immediately or stored for several minutes, days, or months until needed. After the formation of the precursor laminate, the second textile layer can be applied. In this process, a second heat-reactive material layer is applied continuously or discontinuously to the second textile layer, to the carrier layer side of the precursor laminate, or to both, and then the second textile layer can be bonded to the precursor laminate (carrier layer side), for example, using a calender roll. The stepwise process described herein can be carried out in one facility, or possibly in multiple facilities located in different locations. For example, the precursor laminate can be formed in one facility and then transported to a second facility to form the laminate.

[0138] In other embodiments, a continuous lamination process may be used, in which a first heat-reactive material layer is applied to a first textile layer, a carrier layer, or both, and a second heat-reactive material layer is applied to a second textile layer, a carrier layer, or both, and these layers are bonded together in one or more lamination steps, where the first and second textile layers form the outermost layers of the laminate, and the carrier layer forms the inner layer between the outermost layers. In some embodiments, the first and second heat-reactive material layers function as adhesives to bond the laminate layers together.

[0139] In some embodiments, a method for forming a laminate includes i) bonding a first textile layer to a carrier layer with a first heat-reactive material layer to form a precursor laminate, and ii) bonding the precursor laminate to a second textile layer with a second heat-reactive material layer. In other embodiments, a method for forming a laminate includes i) bonding a second textile layer to a carrier layer with a second heat-reactive material layer to form a precursor laminate, and ii) bonding the precursor laminate to a first textile layer with a first heat-reactive material layer.

[0140] The first and second thermally reactive material layers are separated from each other by a carrier layer. When the first and second thermally reactive material layers are in a discontinuous form, such as a series of dots or an array of dots, the dots of the first thermally reactive material layer applied to one side of the carrier layer may be fully aligned, partially aligned, or not aligned with the corresponding dots of the second thermally reactive material layer applied to the opposite side of the carrier layer. As used herein, "fully aligned" means that 10% or less of the surface area of ​​the dots in the first thermally reactive material layer is not aligned with the corresponding surface area of ​​the dots in the second thermally reactive material layer. As used herein, the dots of the first and second thermally reactive material layers are said to be not aligned when 10% or less of the surface area of ​​the dots in the first thermally reactive material layer is aligned with the corresponding surface area of ​​the dots in the second thermally reactive material layer. The dots in the first and second thermally reactive material layers are said to be partially aligned when more than 10% but less than 90% of the surface area of ​​the dots in the first and second thermally reactive material layers exceeds the surface area of ​​the corresponding dots in the second thermally reactive material layer.

[0141] Figure 4 shows examples of aligned, partially aligned, and unaligned dots of a thermally reactive material. Figure 4 shows a carrier layer (40) having dots (31a), (32a), and (33a) of a first thermally reactive material layer on a first surface (40a) of the carrier layer (40), and dots (31b), (32b), and (33b) of a second thermally reactive material layer shown on a second surface (40b) of the carrier layer (40). Thermally reactive material (31b) is an example of an unaligned dot compared to the corresponding dot of the corresponding thermally reactive material (31a). Thermally reactive material (32b) is an example of a partially aligned dot compared to the corresponding dot of the thermally reactive material (32a). Thermally reactive material (33b) is an example of an aligned dot compared to the corresponding dot of the thermally reactive material (33a). While we do not wish to be constrained by theory, it is thought that improving the coherence between dots or lines of the first and second thermally reactive materials can improve air permeability and water vapor transmission rate (MVTR).

[0142] In some embodiments, the first and second thermally reactive material layers are applied in a discontinuous manner having discrete shapes, and at least a portion of the discrete shapes of the first thermally reactive material layer is at least partially aligned with the corresponding discrete shapes of the second thermally reactive material layer. In other embodiments, the first and second thermally reactive material layers are applied in a discontinuous manner having discrete shapes, and at least a portion of the discrete shapes of the first thermally reactive material layer is aligned with the corresponding discrete shapes of the second thermally reactive material layer. In yet another embodiment, the first and second thermally reactive material layers are applied in a discontinuous manner having discrete shapes, and at least a portion of the discrete shapes of the first thermally reactive material layer is not aligned with the corresponding discrete shapes of the second thermally reactive material layer. In yet another embodiment, the first and second thermally reactive material layers are applied in a discontinuous manner having discrete shapes, the discrete shapes of the first thermally reactive material layer include a mixture of aligned shapes, partially aligned shapes, and non-aligned shapes when compared to the corresponding discrete shapes of the second thermally reactive material layer.

[0143] In some embodiments, the laminate has a weight of 500 grams / meter 2 (gsm) or less. In other embodiments, the laminate has a weight of 450 gsm or less, or 425 gsm or less, or 400 gsm or less, or 375 gsm or less, or 350 gsm or less, or 325 gsm or less.

[0144] The laminates described herein can provide lightweight laminates that can provide protection against electric arcs measured according to IEC 61482-2 in the electric arc box test (IEC 61482-1-2:2014) and / or the open arc test (IEC 61482-1-1:2009, Method A). In some embodiments, the laminates described herein comply with the IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 500 gsm or less. In some embodiments, the laminates described herein comply with the IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 475 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 450 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 425 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 400 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 375 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 350 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 325 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 300 gsm or less.In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 275 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 265 gsm or less. In some embodiments, the laminates described herein conform to IEC 61482-1-1:2014 and / or IEC 61482-1-2:2014 standards and have a weight of 250 gsm or less.

[0145] use

[0146] Laminates as described herein can be useful in the manufacture of protective articles. Examples of protective articles include clothing such as shirts, jackets, pants, jumpsuits, overalls, aprons, hats, gloves, and footwear, as well as covers, blankets, and tents. In each of these applications, the laminate should be oriented so that the molten layer faces the potential hazard. For example, when forming a jacket using a laminate, the first textile layer should be oriented to face the outside of the jacket, and the second textile layer should be closer to the wearer, so that when exposed to a high-energy or high-temperature event, the first textile layer is exposed to energy before the second textile layer. [Examples]

[0147] Measurement of weight-average molecular weight

[0148] Molecular weight measurements were performed according to the procedure described in Mead, DW, "Measuring the molecular weight distribution of linear flexible polymers from linear viscoelastic material functions" (Journal of Rheology 1994, 38(6): 1797-1827).

[0149] porosity

[0150] Porosity was expressed as percentage porosity and was determined by subtracting the ratio of the average density of the porous polyethylene membrane to the true density of the polymer from 1 and multiplying the result by 100. For the purposes of this calculation, the true density of polyethylene was assumed to be 0.94 grams / cubic centimeter. The density of the sample was calculated by dividing the sample mass / area by its thickness.

[0151] Girly

[0152] The Girly airflow test was conducted at 6.45 cm under a water pressure of 12.4 cm. 2 A sample of 100cm 3 The time required for air to pass through is measured in seconds. Samples were measured using a Girly Model 4110 automatic densimeter with a Girly Model 4320 automatic digital timer. The reported results are the average of multiple measurements.

[0153] Melting and thermal stability tests This test was used to determine the thermal stability of textile materials. The test was based on the thermal stability test described in Section 8.3 of NFPA 1975 (2004 edition). The test furnace was a hot air circulation oven as specified in ISO 17493. The test was conducted according to ASTM D 751 "Standard Test Methods for Coated Fabrics," using the high-temperature blocking resistance test procedure (Sections 89-93), with the following modifications.

[0154] A borosilicate glass plate measuring 100mm x 100mm x 3 mm (4 inches x 4 inches x 1 / 8 inch) was used.

[0155] The test temperature inside the oven was 280°C ± 5°C. After removing the glass plate from the oven, the test specimens were allowed to cool for at least one hour.

[0156] Sample surfaces that adhered to the glass plate, self-adhered during unfolding, or showed evidence of melting or dripping were determined to be meltable. Samples that did not show evidence of melting were retested (using new material samples) at an internal oven test temperature of 300°C. After removal from the oven and cooling for 1 hour, sample surfaces that adhered to the glass plate, self-adhered during unfolding, or showed evidence of melting or dripping were determined to be meltable. Samples that did not exhibit any of these melting criteria were determined to be non-meltable and / or non-dripping samples (i.e., non-meltable textiles and / or non-dripping textiles).

[0157] TMA expansion test: The expansion of expandable graphite particles was measured using thermomechanical analysis (TMA). The expansion test was performed using a TA Instruments TMA 2940 instrument. A ceramic (alumina) TGA pan with a diameter of approximately 8 mm and a height of approximately 12 mm was used to hold the sample. The bottom of the pan was set to zero using a macro-expansion probe with a diameter of approximately 6 mm. Expandable graphite flakes with a depth of approximately 0.1 to 0.3 mm were placed in the pan, measured using a TMA probe with a compressive load of 0.005 N. The furnace was closed and the initial height of the sample was measured. The furnace was heated from approximately 25°C to 600°C at a heating rate of 10°C / min. The displacement of the TMA probe was plotted against temperature, and the dimensional change normalized by the initial sample height was used as a measure of expansion.

[0158] DSC heat absorption test: The tests were conducted using a TA Instruments Q2000 DSC with a TZERO T® sealed pan. Approximately 3 milligrams (mg) of expandable graphite were placed in each pan. The pan was aerated by pressing the corner of a razor blade into the center to create a vent approximately 2 mm long and less than 1 mm wide. The DSC was equilibrated at 20°C. The samples were then heated from 20°C to 400°C at a rate of 10°C / min. Endothermic values ​​were determined from the DSC curve.

[0159] weight: The weight measurements of the materials were carried out as specified in ASTM D751, Section 10. The given units are grams per square meter.

[0160] The electric arcbox test was performed using IEC 61482-1-2:2014.

[0161] The electric arc box test provides information on the material's performance against the stall curve. A "down" result means the material passed the test in that section, while an "up" result means the material failed the test. The box test also provides a measure of burn time (pass: less than 5 seconds, fail: more than 5 seconds), hole formation (the test material passes this section if there are no holes larger than 5 mm), and an overall pass / fail judgment.

[0162] The open arc test was performed according to IEC 61482-1-1:2009, Method A.

[0163] The data is provided as arc thermal performance values, in calories per square centimeter (cal / cm²). 2 It is provided in units of ).

[0164] Furnace expansion test

[0165] A nickel crucible was heated in a 300°C furnace for 2 minutes. A sample of expandable graphite (approximately 0.5 g) was placed in the crucible and left in the 300°C furnace for 3 minutes. After heating, the crucible was removed from the furnace and allowed to cool. The expanded graphite was then transferred to a graduated cylinder, and its expanded volume was measured. The expansion rate was obtained in cc / g units by dividing the expanded volume by the initial weight of the sample.

[0166] Air permeability test: To test the air permeability of the carrier film layer after heat exposure, a 381 mm (15 inch) square test specimen was clamped to a metal frame and then suspended in a forced-air oven set to 260°C. After 5 minutes of exposure, the test specimen was removed from the oven. After allowing the specimen to cool, its air permeability was measured according to the ISO 9237 (1995) test method.

[0167] Vertical combustion test

[0168] The tests were conducted according to ASTM D6413. Samples were exposed to flame for 12 seconds. The afterflame time was averaged across three samples. Laminates with an afterflame time exceeding 2 seconds were considered flammable. The carbonization length was also determined in this test. Samples were tested in both the warp and weft directions.

[0169] Horizontal combustion test

[0170] The test procedure conformed to ISO 15025, and tests were performed on the front surface of the laminate, and separately on the back surface. The tests provided information on afterflame and its duration in seconds (if any), afterglow, hole formation, presence of combustion debris, and presence of combustion at the top or vertical edge of the material.

[0171] Water vapor transmission rate (MVTR)

[0172] The following describes the test used to measure the water vapor transmission rate (MVTR). This procedure has been proven suitable for testing films, coatings, and coated articles.

[0173] In this method, approximately 70 ml of a solution consisting of 35 parts by weight of potassium acetate and 15 parts by weight of distilled water is placed in a 133 ml polypropylene cup with a 6.5 cm diameter opening. Testing according to the method described in U.S. Patent No. 4,862,730 (Crosby) yields a minimum MVTR of approximately 85,000 g / m². 2A stretched polytetrafluoroethylene (PTFE) membrane, which takes 24 hours to heat-seal, is applied to the mouth of the cup, forming a taut, leak-free, porous barrier that seals in the solution.

[0174] A similar stretched PTFE film is attached to the surface of the water bath. The water bath assembly is controlled to 23°C ± 0.2°C using a temperature control chamber and a circulating water bath.

[0175] The test samples are prepared under conditions of 23°C and 50% relative humidity before the test procedure is performed. The samples are positioned so that the porous polymer membrane is in contact with a stretched polytetrafluoroethylene membrane attached to the surface of a water bath, and are equilibrated for at least 15 minutes before the cup assembly is introduced.

[0176] Weigh the cup assembly to an accuracy of 1 / 1000g and place it upside down in the center of the test sample.

[0177] Water transport is carried out by a driving force between the water and saturated salt solution in the water bath, providing a fluidity of water due to diffusion in that direction. The sample is tested for 15 minutes, then the cup assembly is removed and weighed again with an accuracy of 1 / 1000 g. The MVTR of the sample is calculated from the weight increase of the cup assembly and expressed as grams of water per square meter of sample surface area per 24 hours.

[0178] Edge ignition test

[0179] Edge ignition tests were conducted in accordance with ISO 11612. These tests provided information on afterflames and their duration in seconds (if any), afterglow, hole formation, presence of combustion debris, and presence of combustion at the upper or vertical edge of the material.

[0180] Thermally reactive material 1

[0181] A flame-retardant polyurethane resin was prepared by first forming a resin according to the examples in U.S. Patent No. 4,532,316, owned by the same person, and then adding approximately 20% by mass of a phosphorus-based additive, phosphate ester FYROLFLEX® RDP, in a reactor. After the formation of the polyurethane resin, 65 parts by weight of this polyurethane resin was mixed with 24 parts by weight of expandable graphite (expandable graphite that expands to more than 900 micrometers at 280°C as determined by a TMA expansion test) and 17 parts by weight of another phosphorus-based flame retardant in a stirring vessel at 80°C. The mixture was cooled and used as is.

[0182] Thermally reactive materials 2

[0183] The aqueous, heat-reactive material was prepared by manually mixing 1000 parts by weight of EDOLAN® AM aqueous acrylic resin (available from Tanatex Chemicals in Ede, Netherlands), 175 parts by weight of expandable graphite (expandable graphite that expands more than 900 micrometers at 280°C as determined by TMA expansion test), 175 parts by weight of phosphorus-based flame retardant, 120 parts by weight of glycerin, and 10 parts by weight of RESPUMIT® NF01 defoaming agent. This mixture was manually stirred until relatively homogeneous to form an acrylic mixture.

[0184] Before use, a mixture of 100 parts by weight of ARKOPHOP® DAN crosslinking agent (available from Archroma, Basel, Switzerland), 5 parts by weight of EDOLAN® XTP crosslinking agent, and 10 parts by weight of ACRACONC® FN thickener (available from Tanatex Chemicals, Ede, Netherlands) was manually stirred. This crosslinking agent mixture was added to the acrylic mixture and stirred. This mixture was then used as is.

[0185] Thermally reactive material 3

[0186] The aqueous, heat-reactive material was formed by manually mixing 1000 parts by weight of EDOLAN® AM aqueous acrylic resin (available from Tanatex Chemicals in Ede, Netherlands), 240 parts by weight of expandable graphite (expandable graphite that expands more than 900 micrometers at 280°C as determined by TMA expansion test), 240 parts by weight of phosphorus-based flame retardant, 130 parts by weight of glycerin, and 10 parts by weight of RESPUMIT® NF01 defoaming agent. This mixture was then manually stirred until relatively homogeneous to form an acrylic mixture.

[0187] Before use, a mixture of 130 parts by weight of ARKOPHOP® DAN crosslinking agent (available from Archroma, Basel, Switzerland), 5 parts by weight of EDOLAN® XTP crosslinking agent, and 15 parts by weight of ACRACONC® FN thickener (available from Tanatex Chemicals, Ede, Netherlands) was manually stirred. This crosslinking agent mixture was added to the acrylic mixture and stirred. This mixture was then used as is.

[0188] Thermally reactive material 4

[0189] The aqueous, heat-reactive material was formed by manually mixing 1000 parts by weight of LURAPRET® DS 150 aqueous acrylic resin (available from Archroma in Basel, Switzerland), 240 parts by weight of expandable graphite (expandable graphite that expands more than 900 micrometers at 280°C as determined by TMA expansion testing), 240 parts by weight of phosphorus-based flame retardant, 130 parts by weight of glycerin, and 10 parts by weight of RESPUMIT® NF01 defoaming agent. This mixture was then manually stirred until relatively homogeneous to form an acrylic mixture.

[0190] Before use, a mixture of 130 parts by weight of ARKOPHOP® DAN crosslinking agent (available from Archroma, Basel, Switzerland), 5 parts by weight of EDOLAN® XTP crosslinking agent, and 15 parts by weight of ACRACONC® FN thickener (available from Tanatex Chemicals, Ede, Netherlands) was stirred. This crosslinking agent mixture was added to the acrylic mixture and stirred by hand. This mixture was used as is.

[0191] Polyethylene membrane 1

[0192] A waterproof, breathable, porous polyethylene membrane was prepared in accordance with the jointly owned international patent application publication WO2020 / 028328, which is incorporated herein by reference in its entirety. This porous membrane comprises an ultra-high molecular weight porous polyethylene film, the pores of which are filled with a breathable polyurethane polymer.

[0193] Preparation of Laminate 1

[0194] A meltable layer of 100% recycled polyester knitted fabric (product code RJ47PmbG-T from Na Ya Plastics Corp., Taipei City, Taiwan) was laminated to the carrier layer of polyethylene film 1. The polyethylene film was coated with an adhesive with an adhesive coverage of approximately 40-45% and an adhesive density of 40-45 g / m². 2 The heat-reactive material 1 was gravure printed using a gravure roll having a repeating dot pattern that provided an adhesive application amount of (gsm). The molten layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was placed on the roll and cured for at least 24 hours. A second layer of the heat-reactive material 1 was printed on the exposed side of the carrier layer, i.e., the side opposite the molten layer, using the same gravure printing method as before. The printed second layer of the heat-reactive material was coated with 38% polyester / 60% viscose / 2% antistatic fiber at 75-80 grams / meter 2 A non-flammable jersey knit fabric layer was bonded, and this laminate was rolled between the nip of two rollers. The laminate was then placed on the roll and cured for at least 24 hours.

[0195] Preparation of Laminate 2

[0196] A meltable layer of 100% recycled polyester knitted fabric (Nan Ya Plastics, Taiwan, product number RJ47Pmb) was laminated to a polyethylene film 1 carrier layer. The heat-reactive material 1 was coated with an adhesive of approximately 40-45% and 40-45 g / m². 2 The ePTFE film was gravure printed using a gravure roll having a repeating dot pattern that provided the amount of adhesive to be applied. The molten layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was placed on the roll and cured for at least 24 hours. On the exposed side of the carrier layer, i.e., the side opposite the molten layer, a second layer of heat-reactive material 1 was printed using the same gravure printing method as before, at 93 grams / m² of 65% viscose / 23% TWARON® aramid / 12% polyamide 6. 2 A flame-retardant jersey knit textile layer was bonded to a second printed layer of heat-reactive material, and the laminate was rolled between the nip of two rollers. The laminate was then placed on the roll and cured for at least 24 hours.

[0197] Laminates 1 and 2 were subjected to a Class 1 box arc test. In these tests, the laminates provided protection in which the energy transmitted to the wearer fell below the stall curve.

[0198] Preparation of Laminate 3

[0199] A meltable layer of MGNY08jPF fabric (available from Colorprint Textilveredlungs GmbH in Krefeld, Germany) was laminated to a carrier layer of polyethylene film 1. A heat-reactive material 2 was screen printed onto the ePE film using a 250-micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in an adhesive coverage area of ​​approximately 30.5%. The meltable layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then allowed to cool to room temperature. A second layer of heat-reactive material 2 was printed on the exposed side of the carrier layer, i.e., the side opposite the meltable layer, using the same screen used previously. Then, a textile layer (product code 310.300-000, available from Ames Textiles, Inc. in Christiansburg, Virginia) was bonded to the printed second layer of heat-reactive material, and the laminate was rolled between the nips of two rollers. The laminate was then heated at 160°C for 60 seconds and allowed to cool to room temperature.

[0200] Preparation of Laminate 4

[0201] A meltable layer of 100% polyester 85gsm knitted fabric (product code A04Y036DU, available from Nan Ya Plastics, Taipei, Taiwan) was laminated to a polyethylene film 1 carrier layer. A heat-reactive material 3 was screen printed onto the ePE film using a 250 micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in an adhesive coverage area of ​​approximately 30.5%. The meltable layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then allowed to cool to room temperature. A second layer of heat-reactive material 3 was printed on the exposed side of the carrier layer, i.e., the side opposite the meltable layer, using a 250 micrometer thick screen with a repeating pattern of 1.6 mm holes, resulting in a coverage area of ​​approximately 32.5%. An 80gsm textile layer (available from Live Textil in Portugal) was bonded to a second printed layer of heat-reactive material, and this laminate was rolled between the nips of two rollers. The laminate was then heated first at 100°C for 60 seconds, followed by heating at 160°C for 60 seconds, and allowed to cool to room temperature.

[0202] Preparation of Laminate 5

[0203] A meltable layer B of 100% polyester 85gsm knitted fabric (product code A04Y036DU, available from Nan Ya Plastics, Taipei, Taiwan) was laminated to the carrier layer of polyethylene film 1. A heat-reactive material 3 was screen printed using a 250-micrometer thick screen with a repeating pattern of 1.6 mm holes, resulting in an adhesive coverage area of ​​approximately 32.5%. The meltable layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then allowed to cool to room temperature. A second layer of heat-reactive material 3 was printed on the exposed side of the carrier layer, i.e., the side opposite the meltable layer, using a 250-micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in a coverage area of ​​approximately 30.5%. An 80gsm textile layer (available from Live Textil in Portugal) was bonded to a second printed layer of heat-reactive material, and the laminate was rolled between the nips of two rollers. This laminate was then heated first at 100°C for 60 seconds, followed by heating at 160°C for 60 seconds, and allowed to cool to room temperature.

[0204] Preparation of Laminate 6

[0205] A meltable layer of 100% nylon 6,6 fabric (product code TESF001DK, available from Knopfs & Sohn in Helmbrechts, Germany) was laminated to a carrier layer of polyethylene film 1. A heat-reactive material 3 was screen printed onto the ePE film using a 250-micrometer thick screen with a repeating pattern of 1.6 mm holes, resulting in an adhesive coverage area of ​​approximately 32.5%. The meltable layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then cooled to room temperature. A second layer of heat-reactive material 3 was printed on the exposed side of the carrier layer, i.e., the side opposite the meltable layer, using a 250-micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in a coverage area of ​​approximately 30.5%. A textile layer (product code TEAB001, available from Borgini Jersey Srl, Cassina Rizzardi, Italy) was bonded to a printed second layer of heat-reactive material, and the laminate was rolled between the nip of two rollers. This laminate was first heated at 100°C for 60 seconds, then at 160°C for 60 seconds, and allowed to cool to room temperature.

[0206] Preparation of Laminate 7

[0207] A meltable layer B of 100% polyester 85gsm knitted fabric (product code A04Y036DU, available from Nan Ya Plastics, Taipei, Taiwan) was laminated to the carrier layer of polyethylene film 1. A heat-reactive material 4 was screen printed onto the ePE film using a 250-micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in an adhesive coverage area of ​​approximately 30.5%. The meltable layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then allowed to cool to room temperature. A second layer of heat-reactive material 4 was printed on the exposed side of the carrier layer, i.e., the side opposite the meltable layer, using a 250-micrometer thick screen with a repeating pattern of 1.6 mm holes, resulting in a coverage area of ​​approximately 32.5%. An 80gsm textile layer (available from Life Textile, Helmbrechts, Germany) was bonded to a second printed layer of heat-reactive material, and the laminate was rolled between the nips of two rollers. This laminate was first heated at 100°C for 60 seconds, then at 160°C for 60 seconds, and allowed to cool to room temperature.

[0208] Preparation of Laminate 8

[0209] A molten layer B of 100% polyester 85gsm knitted fabric (product code A04Y036DU, available from Nan Ya Plastics, Taipei, Taiwan) was laminated to the carrier layer of polyethylene film 1. A heat-reactive material 4 was screen printed onto the ePE film using a 250 micrometer thick screen with a repeating pattern of 1.6 mm holes, resulting in an adhesive coverage area of ​​approximately 32.5%. The molten layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then allowed to cool to room temperature. A second layer of heat-reactive material 4 was printed on the exposed side of the carrier layer, i.e., the side opposite the molten layer, using a 250 micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in a coverage area of ​​approximately 30.5%. An 80gsm textile layer (available from Life Textile, Helmbrechts, Germany) was bonded to a second printed layer of heat-reactive material, and the laminate was rolled between the nips of two rollers. This laminate was first heated at 100°C for 60 seconds, then at 160°C for 60 seconds, and allowed to cool to room temperature.

[0210] Preparation of Laminate 9

[0211] A meltable layer of 100% nylon 6,6 fabric (product code TESF001DK, available from Knopfs & Sohn in Helmbrechts, Germany) was laminated to the carrier layer of polyethylene film 1. A heat-reactive material 4 was screen printed onto the ePE film using a 250-micrometer thick screen with a repeating pattern of 1.6 mm holes, resulting in an adhesive coverage area of ​​approximately 32.5%. The meltable layer was placed on top of the carrier layer and rolled between the nips of two rollers. This laminate was heated at 100°C for 60 seconds and then allowed to cool to room temperature. A second layer of heat-reactive material 4 was printed on the exposed side of the carrier layer, i.e., the side opposite the meltable layer, using a 250-micrometer thick screen with a repeating pattern of 1.3 mm holes, resulting in a coverage area of ​​approximately 30.5%. A TEAB001 textile layer (product code TEAB001, available from Borzini Jersey, Cassina Rizzardi, Italy) was bonded to a second printed layer of heat-reactive material, and the laminate was rolled between the nip of two rollers. This laminate was first heated at 100°C for 60 seconds, then at 160°C for 60 seconds, and allowed to cool to room temperature.

[0212] Each laminate from 3 to 9 was subjected to a horizontal combustion test in both the warp and weft directions. Laminate 6 failed in the warp direction. All other laminates passed in both the warp and weft directions. In each of these cases, the heat-reactive material was stirred manually. It is thought that manual stirring prevented sufficient dispersion of the components of the heat-reactive material. These non-uniform dispersions resulted in poor screen printing characteristics and insufficient penetration of the heat-reactive material into each screen pore, which can explain the failure of laminate 6.

Claims

1. a) The first textile layer, b) First thermally reactive material layer, c) Carrier layer containing porous polyethylene, d) A second thermally reactive material layer, and e) The second textile layer, A laminate containing, The first thermally reactive material layer and the second thermally reactive material layer each independently comprise a polymer resin and an expandable graphite, and A laminate in which the first heat-reactive material layer is located between the first textile layer and the carrier layer, and the second heat-reactive material layer is located between the carrier layer and the second textile layer.

2. The laminate according to claim 1, wherein each heat-reactive material layer is applied independently, continuously or discontinuously.

3. The laminate according to claim 1 or 2, wherein each heat-reactive material layer has a pattern shape of discontinuous dots, lines, or grids.

4. The expandable graphite expands by at least about 900 micrometers when heated to about 280°C, as measured by thermomechanical analysis (TMA) expansion test, as described in the laminate according to any one of claims 1 to 3.

5. The laminate according to any one of claims 1 to 4, wherein at least one of the first heat-reactive material layer and the second heat-reactive material layer includes a flame-retardant material.

6. The laminate according to any one of claims 1 to 5, wherein the first textile layer and the second textile layer each contain at least one meltable fiber.

7. The laminate according to any one of claims 1 to 6, wherein the porous polyethylene is expanded ultra-high molecular weight polyethylene.

8. The laminate according to any one of claims 1 to 7, wherein the porous polyethylene comprises pores filled with at least partially hydrophilic polymer.

9. The porous polyethylene has a weight-average molecular weight exceeding 500,000 grams / mol, as described in any one of claims 1 to 8.

10. The laminate according to claim 8, wherein the hydrophilic polymer is polyurethane, polyamide, polyester, polyether, ionomer, or copolymer or combination thereof.

11. The laminate according to any one of claims 1 to 10, wherein layers a) and c) are joined to each other using the first heat-reactive material layer, and layers c) and e) are joined to each other using the second heat-reactive material layer.

12. The laminate according to any one of claims 1 to 11, wherein the first heat-reactive material layer covers 25% or more of the surface of the first textile layer.

13. The laminate according to any one of claims 1 to 12, wherein the second heat-reactive material layer covers 25% or more of the surface of the second textile layer.

14. The laminate according to any one of claims 1 to 13, further comprising one or more additional heat-reactive material layers and one or more additional textile layers, each subsequent additional layer being arranged adjacent to the textile layer.

15. The laminate according to any one of claims 1 to 14, wherein the second textile contains meltable fibers and is considered to be a non-meltable / non-dripping textile based on melt and thermal stability tests.

16. The laminate according to any one of claims 1 to 15, wherein the polymer resin comprises an aqueous acrylic resin.

17. The laminate according to any one of claims 1 to 16, wherein the laminate further comprises a protective layer.

18. The laminate according to claim 17, wherein the protective layer is disposed between the first textile layer and the carrier layer.

19. A method for forming a laminate according to any one of claims 1 to 18, i) Bonding the first textile layer to the carrier layer with the first heat-reactive material between them to form a precursor laminate, and ii) Forming a laminate by bonding the precursor laminate to a second textile layer with a second heat-reactive material between them. Methods that include...

20. An article comprising a laminate according to any one of claims 1 to 18.

21. The article according to claim 20, wherein the article is clothing.